Secondary battery

By drying the lithium-ion battery electrode, fibrotic adhesive and granular negative electrode material are used to solve the problem of electrode layer defects caused by uneven solvent evaporation during the lithium-ion battery manufacturing process, and improve the battery life and fast charging performance.

JP2025504009AActive Publication Date: 2025-02-06LG ENERGY SOLUTION LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024544812
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-14
Filing Date
2023-01-30
Publication Date
2025-02-06
Estimated Expiration
2043-01-30

AI Technical Summary

Technical Problem

During the manufacturing process of existing lithium-ion batteries, uneven adhesive distribution in the electrode layer caused by uneven evaporation of solvents leads to defects on the electrode surface and edges, affecting the battery life and fast charging performance.

Method used

The electrode is manufactured by dry method, by introducing a fibrotic binder into the electrode active material layer and using a granular negative electrode material, the solvent drying step is avoided, and the flexibility and electrochemical reaction rate of the electrode are improved.

Benefits of technology

Improves the battery life characteristics and fast charging performance, reduces initial resistance, enhances the uniformity of the electrode layer and adhesive distribution, and reduces electrode surface defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025504009000001_ABST
    Figure 2025504009000001_ABST
Patent Text Reader

Abstract

The present invention provides a secondary battery including: a positive electrode including a positive electrode current collector; a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, a conductive material, and a binder, the binder being fibrous to bind the positive electrode active material and the positive electrode conductive material; a negative electrode including a negative electrode current collector; and a negative electrode active material layer located on the negative electrode current collector, the negative electrode active material layer including a negative electrode active material and a negative electrode binder, the negative electrode active material layer including a plurality of granules bound by the negative electrode binder; and a separator interposed between the positive electrode and the negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a secondary battery, and more particularly to a secondary battery capable of being rapidly charged and having improved life characteristics.

[0002] This application claims priority to Korean Patent Application No. 10-2022-0013753 filed on January 28, 2022, and Korean Patent Application No. 10-2022-0031625 filed on March 14, 2022, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]

[0003] While the use of fossil fuels is rapidly increasing, the demand for alternative and clean energy is also increasing. As part of this, the field of power generation and storage using electrochemistry is one of the most actively researched fields. Currently, a representative example of an electrochemical element that uses such electrochemical energy is a secondary battery, and its range of use is expanding. A representative secondary battery, a lithium secondary battery, is not only used as an energy source for mobile devices, but has also been used as a power source for electric vehicles and hybrid electric vehicles to replace vehicles that use fossil fuels such as gasoline vehicles and diesel vehicles, which are one of the main causes of air pollution, and its range of use is expanding as an auxiliary power source through gridization.

[0004] The manufacturing process of such a lithium secondary battery can be roughly divided into three steps: an electrode manufacturing process, an electrode assembly manufacturing process, and a chemical formation process. The electrode manufacturing process can be further divided into an electrode mixture mixing process, an electrode coating process, a drying process, a rolling process, a slitting process, a winding process, etc.

[0005] Among these, the electrode mixture mixing process is a process of blending components for forming an electrode active layer where an electrochemical reaction actually occurs in the electrode. In detail, it is a process of mixing an electrode active material, which is an essential element of an electrode, other additives such as a conductive material and a filler, a binder for binding between powder particles and for adhesion to a current collector, and a solvent for imparting viscosity and dispersing powder, to produce a slurry having fluidity.

[0006] The slurry is applied onto an electrically conductive current collector in an electrode coating process, and then a drying process is performed to remove the solvent contained in the electrode mixture slurry. The electrode is then rolled to produce an electrode of a desired thickness.

[0007] In such a conventional electrode manufacturing process, in the drying process for drying the solvent contained in the slurry, there is a drawback in that the materials, especially the binder, migrate to the surface of the electrode due to non-uniform shrinkage of the electrode or differences in the evaporation rate of the solvent, resulting in non-uniform distribution of the binder in the thickness direction of the electrode layer. This causes problems such as surface defects, edge defects, and reduced adhesion to the current collector. Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention has been made to solve the above problems, and has an object to provide a secondary battery which is capable of being rapidly charged and has improved life characteristics. [Means for solving the problem]

[0009] In order to achieve the above object, according to one aspect of the present invention, there is provided a secondary battery according to the following embodiment.

[0010] According to the first embodiment, a positive electrode including a positive electrode current collector; and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, a positive electrode conductive material, and a positive electrode binder, the positive electrode binder being fibrous to bind the positive electrode active material and the positive electrode conductive material; a negative electrode including: a negative electrode current collector; and a negative electrode active material layer located on the negative electrode current collector, the negative electrode active material layer including a plurality of granules including a negative electrode active material and a negative electrode binder, the negative electrode active material being bound by the negative electrode binder; A secondary battery is provided, the secondary battery including a separator interposed between the positive electrode and the negative electrode.

[0011] According to the second embodiment, in the first embodiment, The positive electrode may have a bending resistance of less than 10 mm in diameter (Φ).

[0012] According to the third embodiment, in the second embodiment, The flex resistance of the positive electrode can be evaluated by the method of measurement standard JIS K5600-5-1.

[0013] According to the fourth embodiment, in the second or third embodiment, The flex resistance of the positive electrode is producing a rectangular cathode sample of 100 mm x 50 mm; preparing measuring rods having diameters of 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 8 mm, 10 mm, 12 mm, 16 mm, 20 mm, 25 mm, and 32 mm, respectively, bringing the positive electrode sample into contact with the measuring rod having the largest diameter among the measuring rods, and then lifting both ends of the positive electrode sample to determine whether cracks are generated in the composite film of the positive electrode sample; If no cracks occur in the previous step, the step of determining whether or not cracks occur in the composite film of the positive electrode sample in the same manner as in the previous step is repeated using a measuring rod with a next larger diameter, and the minimum diameter value of the measuring rod at which no cracks occur in the composite film of the positive electrode sample is determined as the bending resistance.

[0014] According to the fifth embodiment, in any one of the first to fourth embodiments, The positive electrode active material layer may have a porosity of 20% to 35%.

[0015] According to the sixth embodiment, in any one of the first to fifth embodiments, The positive electrode active material loading amount of the positive electrode active material layer is 3 mAh / cm 2 ~15mAh / cm 2 It could be.

[0016] According to the seventh embodiment, in any one of the first to sixth embodiments, The interface resistance between the positive electrode active material layer and the positive electrode current collector is 5 Ω cm 2 It can be the following:

[0017] According to the eighth embodiment, in any one of the first to seventh embodiments, The positive electrode binder included in the positive electrode active material layer may have a crystallinity of 10% or less.

[0018] According to the ninth embodiment, in any one of the first to eighth embodiments, the positive electrode active material layer includes a positive electrode active material, a positive electrode conductive material, and a fluorine-based positive electrode binder; the positive electrode active material layer has a positive electrode QBR (Quantified Binder Ratio) of 1.1 or less, The positive electrode QBR is represented by the following formula 1: [Formula 1] Positive electrode QBR=CBs / CBf may be defined as In Formula 1, CBs represents the average value of the fluorine content in a surface region of the positive electrode active material layer from the outermost surface of the positive electrode active material layer to within 15% of the total thickness of the positive electrode active material layer, and CBf represents the average value of the fluorine content in a bottom region of the positive electrode active material layer from the interface of the positive electrode active material layer facing the positive electrode current collector to within 15% of the total thickness of the positive electrode active material layer.

[0019] According to the tenth embodiment, in any one of the first to ninth embodiments, The binder contained in the positive electrode active material layer may include polytetrafluoroethylene (PTFE).

[0020] According to the eleventh embodiment, in any one of the first to tenth embodiments, The conductive material contained in the positive electrode active material layer may include activated carbon, graphite, carbon black, Ketjen black, carbon nanotubes, or two or more of these.

[0021] According to the twelfth embodiment, in any one of the first to eleventh embodiments, The positive electrode active material layer may contain 85 to 98 parts by weight of a positive electrode active material, 0.5 to 5 parts by weight of a conductive material, and 0.5 to 10 parts by weight of a binder.

[0022] According to the thirteenth embodiment, in any one of the first to twelfth embodiments, The positive electrode current collector may be entirely or partially coated with a conductive primer. According to the 14th embodiment, in any one of the 1st to 13th embodiments, The positive electrode may be a dry electrode produced by a dry process.

[0023] According to the fifteenth embodiment, in any one of the first to fourteenth embodiments, The positive electrode is preparing a mixture including a positive electrode active material, a conductive material, and a binder; Kneading the mixture at a temperature in the range of 70°C to 200°C under a pressure equal to or higher than normal pressure to produce a mixture mass; pulverizing the mixture mass to obtain a positive electrode mixture powder; The positive electrode mixed powder is put between a plurality of rolls and calendered to form a positive electrode film; and laminating the positive electrode film onto a metal current collector.

[0024] According to the sixteenth embodiment, in the fifteenth embodiment, The step of kneading to prepare a mixture mass may be carried out in a kneader under pressure equal to or higher than atmospheric pressure.

[0025] According to the seventeenth embodiment, in the fifteenth or sixteenth embodiment, The compression ratio of the positive electrode film in the lamination step may be 30 to 50%.

[0026] According to the 18th embodiment, in any one of the 15th to 17th embodiments, The rolling ratio of the positive electrode film may be 20% or less.

[0027] According to the 19th embodiment, in any one of the 15th to 18th embodiments, The increase in apparent density before and after lamination of the positive electrode film and the current collector may be 5% to 30%.

[0028] According to the 20th embodiment, in any one of the 15th to 19th embodiments, The lamination step may be performed by using a lamination roll at 25°C to 250°C.

[0029] According to the 21st embodiment, in any one of the 1st to 19th embodiments, The granules included in the negative electrode may have a central portion including the negative electrode active material, and a surface portion located entirely or partially outside the central portion and including a binder binding the negative electrode active material.

[0030] According to the 22nd embodiment, in any one of the 1st to 21st embodiments, The binder contained in the surface portions of the plurality of granules may be connected to the binder contained in the surface portions of adjacent granules, so that the binder may be distributed in a network structure within the active material layer.

[0031] According to the 23rd embodiment, in any one of the 1st to 22nd embodiments, the negative electrode active material layer includes a negative electrode active material and a negative electrode binder, the negative electrode binder has a double bond, the negative electrode active material layer has a negative electrode QBR (Quantified Binder Ratio) of 2.0 or less, The negative electrode QBR is represented by the following formula 2: [Formula 2] Negative electrode QBR=ABs / ABf may be defined as In Formula 2, ABs represents the average value of the double bond content of the negative electrode binder in a surface region of the negative electrode active material layer from the outermost surface of the negative electrode active material layer to within 15% of the total thickness of the negative electrode active material layer, and ABf represents the average value of the double bond content of the negative electrode binder in a bottom region of the negative electrode active material layer from the interface of the negative electrode active material layer facing the negative electrode current collector to within 15% of the total thickness of the negative electrode active material layer.

[0032] According to the 24th embodiment, in any one of the 1st to 23rd embodiments, The granules are The content (wt%) of the electrode binder relative to the total weight (100 wt%) of the negative electrode active material and the negative electrode binder is higher in the surface portion than in the center portion, The surface portion is a region near the surface of the granule from the surface of the granule to a predetermined depth toward the center of the granule, and the central portion may be a portion other than the surface portion.

[0033] According to the 25th embodiment, in any one of the 1st to 24th embodiments, The negative electrode binder may include a diene-based polymer, an acrylate-based polymer, a styrene-based polymer, or two or more of these.

[0034] According to the 26th embodiment, in any one of the 1st to 25th embodiments, The negative electrode active material layer may include a plurality of granules including a negative electrode active material, a negative electrode conductive material, and a negative electrode binder, the negative electrode active material and the negative electrode conductive material being bound by the negative electrode binder.

[0035] According to the 27th embodiment, in the 26th embodiment, The negative electrode conductive material may include activated carbon, graphite, carbon black, Ketjen black, carbon nanotubes, or two or more thereof.

[0036] According to the 28th embodiment, in the 26th or 27th embodiment, The negative electrode active material layer may contain 85 to 98 parts by weight of a negative electrode active material, 0.5 to 5 parts by weight of a negative electrode conductive material, and 0.5 to 10 parts by weight of a negative electrode binder.

[0037] According to the 29th embodiment, in any one of the 1st to 28th embodiments, A primer layer may be formed on at least one surface of the negative electrode current collector, the primer layer may include a binder and a conductive material, and the sum of the content of the binder and the content of the conductive material may be 90 wt % or more based on the total weight of the primer layer.

[0038] According to the 30th embodiment, in any one of the 1st to 29th embodiments, The negative electrode is mixing a negative electrode active material and a negative electrode binder with a dispersion medium to prepare a slurry; spray drying the slurry to produce initial granules; Spreading the initial granules on a current collector; and rolling the applied initial granules to form a negative electrode active material layer including the rolled granules.

[0039] According to the 31st embodiment, in any one of the 1st to 30th embodiments, The slurry may further include a negative electrode conductive material.

[0040] According to the 32nd embodiment, An energy storage device including a secondary battery according to any one of the first to thirty-first embodiments as a unit battery is provided. Effect of the Invention

[0041] In a secondary battery according to an embodiment of the present invention, a dry electrode is applied to both the positive and negative electrodes, which is manufactured without a process of drying a solvent when an active material layer is formed on a current collector. Compared to a conventional secondary battery in which a wet electrode, which requires a process of drying a solvent when an active material layer is formed on a current collector, is applied to at least one of the positive and negative electrodes, the secondary battery can exhibit low initial resistance, low voltage rise during fast charging, and improved life characteristics.

[0042] Specifically, the secondary battery according to one embodiment of the present invention includes a positive electrode using a fiberized binder and a negative electrode manufactured using the granules. The positive electrode using the fiberized binder has improved electrochemical reaction rate characteristics, and the negative electrode manufactured using the granules has a correspondingly faster reaction rate. As a result, the electrochemical reaction rate of the positive electrode and the electrochemical reaction rate of the negative electrode are balanced, and the overall life characteristics of the secondary battery can be significantly improved.

[0043] The following drawings attached to this specification illustrate preferred embodiments of the present invention and, together with the detailed description of the invention, serve to further understand the technical ideas of the present invention. The present invention should not be interpreted as being limited only to the matters described in the drawings. [Brief description of the drawings]

[0044] [Figure 1] FIG. 2 is a schematic diagram of an electrode according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a schematic diagram of calculating the QBR value of an electrode layer. [Diagram 3] 1 is a schematic diagram of a process for producing a positive electrode film according to one embodiment of the present invention. FIG. [Figure 4] FIG. 2 is a schematic diagram of an electrode lamination process according to one embodiment of the present invention. [Diagram 5]FIG. 2 is a schematic diagram of the surface and core of a granule according to one embodiment of the present invention. [Figure 6] 1 is a photographic image of granules immobilized within a cured epoxy resin. [Figure 7] 1 is a SEM image of the granular particles prepared in Example 1 of the present invention. [Figure 8] 1 is a graph showing the initial discharge resistance for each SOC (State Of Charge) of secondary batteries manufactured in Example 1, Comparative Example 1, and Comparative Example 2. [Figure 9] 1 is a graph showing the initial charging resistance for each SOC of secondary batteries manufactured in Example 1, Comparative Example 1, and Comparative Example 2. [Figure 10] 1 is a graph showing voltage rise changes during rapid charging of secondary batteries manufactured in Example 1, Comparative Example 1, and Comparative Example 2. [Figure 11] 1 is a graph showing 200 cycle life characteristics of secondary batteries manufactured in Example 1, Comparative Example 1, and Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0045] The present invention will now be described in more detail to aid in understanding the present invention. The terms and words used in this specification and claims should not be interpreted limited to their ordinary and dictionary meanings, but should be interpreted in a meaning and concept that corresponds to the technical idea of ​​the present invention, based on the principle that the inventor himself can appropriately define the concept of the term in order to explain the invention in the best possible way.

[0046] The terms used in this specification are used to describe exemplary embodiments and are not intended to limit the present invention. Unless otherwise specified, the singular expression includes the plural expression.

[0047] Furthermore, throughout the specification, when a part "comprises" another component, it does not mean excluding the other component, but means that the other component may be further included, unless otherwise specified.

[0048] In addition, the terms "about," "substantially," and the like used throughout this specification are used to mean a numerical value or a value close to the numerical value when manufacturing and material tolerances inherent in the referred meaning are given, and are used to prevent unscrupulous infringers from unfairly using the starting content in which an exact or absolute numerical value is mentioned to facilitate understanding of this application.

[0049] Throughout this specification, the phrase "A and / or B" means "A, B, or all of these."

[0050] Certain terminology is used herein for convenience and not for limitation. Terms such as "top," "bottom," "front," "back," "inside," and "outside" are used to describe relative positions and orientations between components, rather than absolute positions, or to indicate positions and orientations in the drawings to which reference is made. The above terms include not only themselves, but also words containing them, derivatives thereof, and words of similar import.

[0051] As used herein, the term "glass transition temperature (T g )" is measured by a conventional method known in the art, and may be measured, for example, by Differential Scanning Calorimetry (DSC). In the present specification, the term "porosity" refers to the ratio of the volume of pores to the total volume of a structure, and is expressed in vol%. It may be used interchangeably with terms such as porosity and porosity. In the present invention, the measurement of the porosity is not particularly limited, and may be measured, for example, by BET (Brunauer-Emmett-Teller) measurement using nitrogen gas or mercury intrusion porosimetry, and ASTM D-2873, according to one embodiment of the present invention. Alternatively, the true density of the separator may be calculated from the density of the separator (apparent density), the composition ratio of the materials contained in the separator, and the density of each component, and the porosity of the separator may be calculated from the difference between the apparent density and the true density.

[0052] As used herein, the term "average particle size (D50)" refers to the particle size at 50% of the cumulative particle number distribution according to the particle size, and the particle size may be measured using a laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), and the particle size distribution is calculated by measuring the difference in the diffraction pattern according to the particle size when the particles pass through a laser beam. The D50 particle size can be measured by calculating the particle diameter at the 50% point of the cumulative particle number distribution according to the particle size using the measuring device.

[0053] The "thickness" of each layer included in the electrode used in this specification may refer to a value measured by a known method for measuring thickness. The thickness may be measured, for example, using a thickness meter (Mitutoyo Corporation, VL-50S-B), but is not limited thereto.

[0054] The "specific surface area" as used herein may refer to a value measured by a known method for measuring the specific surface area. The specific surface area may be measured, for example, by a flow or stationary method, but is not limited thereto.

[0055] The present invention relates to an electrode and an electrochemical device including the electrode. The electrochemical device of the present invention includes any device that performs an electrochemical reaction, specifically, all kinds of primary batteries, secondary batteries, fuel cells, solar cells, or capacitors such as supercapacitor devices. In the present invention, the electrochemical device may preferably be a secondary battery, more preferably a lithium ion secondary battery.

[0056] Conventionally, a process for manufacturing positive and negative electrodes for secondary batteries includes a step of applying a slurry containing an active material, a binder, a conductive material, and a solvent (dispersion medium) onto at least one surface of a current collector, and a drying step of drying the dispersion medium contained in the slurry. An electrode manufactured by such an electrode manufacturing process is called a wet electrode. Such a wet electrode has a drawback that the binder is migrated to the surface of the electrode due to uneven shrinkage of the electrode or a difference in the evaporation rate of the solvent, resulting in uneven distribution of the binder in the thickness direction of the electrode layer, as a result of the drying step during manufacturing. This results in poor shape of the surface and end of the electrode or a decrease in adhesive strength between the electrode layer and the current collector, and as a result, secondary batteries equipped with such wet electrodes as positive and negative electrodes have limitations in terms of life characteristics, rapid charging characteristics, and resistance characteristics.

[0057] In an attempt to solve the problems of the conventional secondary battery having wet electrodes, the present inventors have invented a secondary battery including, as a positive electrode and a negative electrode, dry electrodes manufactured by a dry process that does not require a drying process for removing a solvent when forming an active material layer on a current collector. In particular, the positive electrode and the negative electrode included in the secondary battery of the present invention are electrodes manufactured by different dry electrode manufacturing methods and have different configurations and structures. Specifically, the positive electrode is a dry electrode type in which a fiberized binder is introduced into the positive electrode active material layer to bind the active material, and the negative electrode is a dry electrode type in which a number of granules including the active material and the binder are introduced into the negative electrode active material layer.

[0058] The fiberized binder applied to the positive electrode reacts with lithium ions in the negative electrode operating potential region of the lithium secondary battery, reducing the efficiency of the entire secondary battery, and therefore it is technically very difficult to apply the fiberized binder applied to the positive electrode to the negative electrode as well.

[0059] Meanwhile, when the method of manufacturing granules for use in the negative electrode is applied to the positive electrode, if an organic solvent such as N-methyl-2-pyrrolidone (NMP) is used as a dispersion medium in the step of preparing granules for the positive electrode active material by drying the slurry for the positive electrode using a spray dryer, there is a risk of explosion due to the high boiling point of the organic solvent, and if an aqueous solvent such as water is used as a dispersion medium, there is a problem of a decrease in cell capacity. Furthermore, since the granules for use in the negative electrode have high hardness and the positive electrode active material is sensitive to external forces, there is a limit in that an appropriate level of pressure cannot be applied during rolling when such granules are used to manufacture a positive electrode. Therefore, it is more advantageous to use a fiberized binder that can be manufactured even at a relatively low pressure when manufacturing a positive electrode.

[0060] In view of the above, according to one embodiment of the present invention, a positive electrode including a positive electrode current collector; and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, a positive electrode conductive material, and a positive electrode binder, the positive electrode binder being fibrous to bind the positive electrode active material and the positive electrode conductive material; a negative electrode including: a negative electrode current collector; and a negative electrode active material layer located on the negative electrode current collector, the negative electrode active material layer including a plurality of granules including a negative electrode active material and a negative electrode binder, the negative electrode active material being bound by the negative electrode binder; A separator interposed between the positive electrode and the negative electrode is provided.

[0061] The positive electrode and the negative electrode contained in the secondary battery of the present invention will be described in detail below. The positive electrode includes a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, a positive electrode conductive material, and a positive electrode binder, the positive electrode binder being fibrous to bind the positive electrode active material and the positive electrode conductive material.

[0062] The positive electrode of the present invention contains a fibrous binder as a means for binding the positive electrode active material and the positive electrode conductive material in the positive electrode active material layer, and such a fibrous binder is less likely to be cut than a conventional non-fibrous binder and has excellent extensibility in the longitudinal direction, so that the flexibility of the positive electrode active material layer and the positive electrode itself including the same can be significantly improved. The fiberization process of the binder will be specifically described in the manufacturing method of the positive electrode described later.

[0063] The positive electrode active material is not limited as long as it is in the form of a lithium transition metal oxide, lithium metal iron phosphate, or metal oxide, and for example, lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), or compounds substituted with one or more transition metals; 1+x Mn 2-x O 4 (x is 0 to 0.33), LiMnO 3 , LiMn 2 O 3 , LiMnO 2 Lithium manganese oxides such as lithium copper oxide (Li 2 CuO 2 );LiV 3 O 8 , LiV 3 O 4 , V 2 O 5 , Cu 2 V 2 O 7 Vanadium oxides such as LiNi 1-x M x O 2 (M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, x=0.01-0.3) Ni-site type lithium nickel oxide; chemical formula LiMn 2-x M x O 2 (M=Co, Ni, Fe, Cr, Zn or Ta, x=0.01~0.1) or Li 2 Mn 3 MO 8Lithium manganese composite oxide represented by (M=Fe, Co, Ni, Cu or Zn); Li in which part of the Li in the chemical formula is replaced by aluminum ions 1+x (Ni a Co b Mn c Al d ) 1x O 2 (x=0~0.03, a=0.3~0.95, b=0.01~0.35, c=0.01~0.5, d=0.001~0.03, a+b+c+d=1); Lithium metal phosphate LiMPO 4 (M=Fe, CO, Ni or Mn), disulfide compounds; Fe 2 (MoO 4 ) 3 These include, but are not limited to, the following:

[0064] The positive electrode conductive material is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity. For example, graphite such as natural graphite and artificial graphite; carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fiber and metal fiber; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives may be used. More specifically, in order to uniformly mix the conductive material and improve the conductivity, the positive electrode conductive material may include one or more selected from the group consisting of activated carbon, graphite, carbon black, and carbon nanotubes, and more specifically, may include activated carbon.

[0065] The positive electrode binder can include polytetrafluoroethylene (PTFE), a polyolefin, or a mixture thereof, specifically, can include polytetrafluoroethylene (PTFE), and more specifically, can be polytetrafluoroethylene (PTFE).

[0066] Specifically, the polytetrafluoroethylene (PTFE) may be contained in an amount of 60% by weight or more based on the total weight of the binder.

[0067] Of course, the positive electrode binder may further include polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), and the like.

[0068] According to one embodiment of the present invention, the content of the positive electrode active material may be 85 to 98 parts by weight, the content of the positive electrode conductive material may be 0.5 to 5 parts by weight, and the content of the positive electrode binder may be 0.5 to 10 parts by weight. Also, the content of the positive electrode active material may be 90 to 98 parts by weight, the content of the positive electrode conductive material may be 0.5 to 5 parts by weight, and the content of the positive electrode binder may be 0.5 to 5 parts by weight.

[0069] When the contents of the positive electrode active material, the positive electrode conductive material, and the positive electrode binder satisfy these ranges, the positive electrode binder can be sufficiently fibrous in a subsequent kneading process to form a mixture mass, an electrode film can be easily manufactured by molding the mixed powder formed in the pulverization process, the physical properties of the electrode film can be ensured, the content of the positive electrode active material can be ensured to prevent a problem of capacity reduction, and sufficient conductivity can be ensured.

[0070] Meanwhile, depending on the case, a filler, which is a component that suppresses the expansion of the electrode, may be further added to the mixture. The filler is not particularly limited as long as it does not induce chemical changes in the battery and is a fibrous material, and for example, olefin polymers such as polyethylene and polypropylene; glass fiber, carbon fiber, and other fibrous materials may be used.

[0071] According to one embodiment of the present invention, the flex resistance of the positive electrode may be a diameter (Φ) of less than 10 mm, 8 mm or less, 5 mm or less, 2 mm to 8 mm, 2 mm to 5 mm, or 2 mm to 3 mm.

[0072] The bending resistance can be evaluated by the method of measurement standard JIS K5600-5-1. Specifically, the positive electrode is brought into contact with measuring rods of various diameters, and then both ends are lifted up to measure whether cracks occur in the positive electrode active material layer and the minimum diameter at which no cracks occur.

[0073] According to one embodiment of the present invention, the flex resistance of the positive electrode is producing a rectangular electrode sample of 100 mm x 50 mm; preparing measuring rods having diameters of 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 8 mm, 10 mm, 12 mm, 16 mm, 20 mm, 25 mm, and 32 mm, respectively, bringing the positive electrode sample into contact with the measuring rod having the largest diameter among them, and then lifting both ends of the electrode sample to determine whether cracks are generated in the composite film of the positive electrode sample;

[0074] If no cracks occur in the previous step, the step of determining whether or not cracks occur in the composite film of the positive electrode sample in the same manner as in the previous step is repeated using a measuring rod with a next larger diameter, and the minimum diameter value of the measuring rod at which no cracks occur in the composite film of the positive electrode sample is determined as the bending resistance.

[0075] The loading amount of the positive electrode active material layer is 3 mAh / cm 2 ~15mAh / cm 2 Specifically, 4 mAh / cm 2 ~10mAh / cm 2 , 4mAh / cm 2 ~6mAh / cm 2 , 4mAh / cm 2 ~5mAh / cm 2 , or 4.8mAh / cm 2 ~4.9mAh / cm 2 It could be.

[0076] Here, the active material loading amount is a value calculated as follows. Loading capacity (mAh / cm 2) = [Capacity of active material (mAh / g)] × [Weight ratio of active material in the composite film (wt%) × Weight per unit area of ​​the composite film (g / cm 2 )]

[0077] The interface resistance between the positive electrode active material layer and the current collector is 5 Ω cm 2 Below, 4.3Ω cm 2 Below, 4Ω cm 2 Below, 3Ω cm 2 Below, 1.3Ω cm 2 ~4.3 Ω cm 2 , 1.3 Ω cm 2 ~1.8 Ω cm 2 , or 1.8 Ω cm 2 ~4.3 Ω cm 2 It could be.

[0078] Here, the interfacial resistance was measured by applying a current of 100 μA to the positive electrode using a multi-probe resistance measurement method, and calculating the resistance between the positive electrode active material layer and the current collector layer based on the potential difference measured between 46 probes.

[0079] If the interface resistance is too high and falls outside the above range, this is not preferred because it may degrade the battery performance of the secondary battery produced subsequently.

[0080] Meanwhile, the current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, calcined carbon, copper, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. In addition, the current collector may have fine irregularities on its surface to increase the adhesive force of the positive electrode active material, and may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0081] Furthermore, the current collector may be entirely or partially coated with a conductive primer on its surface to reduce resistance and improve adhesion.

[0082] Here, the conductive primer may include a conductive material and a binder. The conductive material may be, but is not limited to, any material having electrical conductivity, and may be, for example, a carbon-based material.

[0083] The binder may include solvent-soluble fluorine-based binders (including PVDF and PVDF copolymers), acrylic binders, water-based binders (including diene-based rubbers such as styrene butadiene rubber (SBR) and nitrile butadiene rubber (NBR)), and the like.

[0084] The porosity of the positive electrode active material layer of the positive electrode may be 20% to 50%, 20% to 45%, 20% to 40%, 20% to 35%, 22% to 30%, 20% to 28%, 20% to 26%, 23.1% to 27.4%, 23.1% to 24.8%, or 24.8% to 27.4%. Such porosity may be changed slightly depending on the effect to be emphasized.

[0085] However, when the porosity of the positive electrode active material layer is within this range, the electrolyte impregnation is improved, resulting in excellent life characteristics and output characteristics, and there is no need to increase the volume to achieve the same capacity, which is advantageous in terms of energy density per volume.

[0086] The porosity of the positive electrode active material layer can be calculated by subtracting the volume and weight of the current collector from the volume and weight of the electrode to calculate the apparent density of only the composite film, and using the true density calculated based on the true density and composition of each component, according to the following formula: Porosity (%) = {1-(apparent density / true density)} x 100

[0087] In an embodiment of the present invention, the positive electrode binder in the positive electrode active material layer may have a crystallinity of 10% or less.

[0088] In the present invention, the crystallinity (Xc) can be measured using a differential scanning calorimeter (DSC) and is based on the temperature (peak temperature) at which the highest enthalpy is observed during crystallization. Specifically, the crystallinity is expressed in percentage by multiplying the melting enthalpy (ΔHm) value actually measured by DSC by the melting enthalpy (ΔHm0) (equilibrium heat of fusion) value of a theoretical perfect crystal (crystallinity 100%), and can be calculated by the following formula. Here, the melting enthalpy value of a theoretical perfect crystal is found in the polymer handbook for known polymers, and can be calculated by extrapolation by extending the crystallinity at two or more points for unknown or newly synthesized materials. Xc(%)=(ΔH m ÷ΔH m 0 ) x 100

[0089] According to one embodiment of the present invention, the positive electrode active material layer includes a positive electrode active material, a positive electrode conductive material, and a fluorine-based positive electrode binder, The positive electrode active material layer may have a positive electrode Quantified Binder Ratio (QBR) of 1.1 or less.

[0090] The positive electrode QBR is defined by the following Equation 1. [Formula 1] Positive electrode QBR=CBs / CBf

[0091] In Formula 1, CBs represents the average value of the fluorine content in a surface region of the positive electrode active material layer from the outermost surface of the positive electrode active material layer to within 15% of the total thickness of the positive electrode active material layer, and CBf represents the average value of the fluorine content in a bottom region of the positive electrode active material layer from the interface of the positive electrode active material layer facing the positive electrode current collector to within 15% of the total thickness of the positive electrode active material layer.

[0092] 1 is a schematic diagram of a positive electrode according to one embodiment of the present invention. Referring to FIG 1, a positive electrode 10 includes a positive electrode current collector 12 and a positive electrode active material layer 11 located on the positive electrode current collector 12 and including a positive electrode active material, a positive electrode conductive material, and a fluorine-containing positive electrode binder.

[0093] The positive electrode active material layer 11 has a surface region 11s of the positive electrode active material layer that extends from the outermost surface of the positive electrode active material layer to within 15% of the total thickness d of the positive electrode active material layer, and a bottom region 11f of the positive electrode active material layer that extends from the interface of the positive electrode active material layer that faces the positive electrode current collector to within 15% of the total thickness d of the positive electrode active material layer, based on the total thickness d.

[0094] In the positive electrode QBR of Formula 1 above, CBs means the average fluorine content in surface region 11s of the positive electrode active material layer, and CBf means the average fluorine content in bottom region 11f of the positive electrode active material layer.

[0095] In this case, the positive electrode QBR can be calculated as follows. First, a cathode for which the cathode QBR is to be confirmed is selected, and a cross section of the selected cathode is prepared using Ar ion milling.Then, an energy dispersive X-ray spectroscopy (EDS) detector of a scanning electron microscope (SEM) is used to perform EDS mapping of the components in the cathode active material layer of the prepared cathode cross section.

[0096] From the EDS mapping results, a line profile in the thickness direction of the positive electrode layer is extracted. From the extracted line profile results, the average fluorine content (Bs) of the fluorine-containing positive electrode binder in the surface region of the positive electrode layer and the average fluorine content (Bf) of the fluorine-containing positive electrode binder in the bottom region of the positive electrode layer are extracted, and the positive electrode QBR value is calculated using the following Equation 1. [Formula 1] Positive electrode QBR=CBs / CBf

[0097] In this case, the surface region of the positive electrode active material layer is a region from the outermost surface in the thickness direction of the positive electrode active material layer to within 15% of the total thickness of the positive electrode active material layer, and the bottom region of the positive electrode active material layer is a region from the interface of the positive electrode active material layer facing the current collector to within 15% of the total thickness of the positive electrode active material layer.

[0098] 2 is a schematic diagram for calculating the positive electrode QBR value of the positive electrode active material layer. Referring to FIG. 2, the X-axis indicates the thickness of the positive electrode active material layer, i.e., the distance from the surface toward the current collector, and the Y-axis indicates the intensity of the fluorine component. Line A indicates the intensity of the fluorine component of the fluorine-containing binder extracted by EDS mapping of the fluorine component in the positive electrode active material layer of the positive electrode cross section, and line B is a trend line showing the tendency of line A, which is a line smoothed by the LOWESS smoothing method, i.e., the locally weighted scatterplot smoothing method.

[0099] The positive electrode QBR value is a value indicating the uniformity of the distribution of the fluorine-containing positive electrode binder in the thickness direction in the positive electrode active material layer through the ratio of the content of the fluorine-containing positive electrode binder contained in the surface region to the content of the fluorine-containing positive electrode binder contained in the bottom region of the positive electrode active material layer. Here, the content of the fluorine-containing positive electrode binder can be estimated through the fluorine component contained in the fluorine-containing positive electrode binder used.

[0100] The positive electrode QBR value is 1.1 or less, and according to one embodiment of the present invention, the QBR value may be 0.95 or more, 0.97 or more, 1.03 or less, 1.05 or less, or may be 0.95 to 1.05.

[0101] When the positive electrode QBR value is in the range of 1.1 or less, the content of the fluorine-containing positive electrode binder contained in the surface region of the positive electrode active material layer is not greater than the content of the fluorine-containing positive electrode binder contained in the bottom region of the positive electrode active material layer due to migration of the fluorine-containing positive electrode binder to the surface of the positive electrode, and therefore the distribution of the binder in the thickness direction of the positive electrode active material layer is uniform. As a result, the adhesive strength between the current collector and the positive electrode active material layer is improved, and the electrical conductivity at the surface of the positive electrode active material layer and the charge / discharge rate therefor are also advantageously increased.

[0102] According to one embodiment of the present invention, the positive electrode may be prepared by a method including the following steps.

[0103] preparing a mixture including a positive electrode active material, a positive electrode conductive material, and a positive electrode binder; kneading the mixture at a temperature in the range of 70° C. to 200° C. under a pressure equal to or higher than normal pressure to produce a mixture mass; pulverizing the mixture mass to obtain a positive electrode mixture powder; the positive electrode mixed powder is put between a plurality of rolls and calendered to form a positive electrode film; The positive electrode film is laminated onto a metal current collector.

[0104] Hereinafter, a method for manufacturing a positive electrode according to one embodiment of the present invention will be described in more detail. First, a mixture containing a positive electrode active material, a positive electrode conductive material, and a positive electrode binder is prepared.

[0105] At this time, the mixing for preparing the mixture is performed so that the positive electrode active material, the positive electrode conductive material, and the positive electrode binder are uniformly distributed, and since they are mixed in the form of powder, they may be mixed in various ways that allow simple mixing of them. However, since the positive electrode of the present invention is prepared by a dry preparation method that does not use a dispersion medium, the mixing may be performed by dry mixing, and may be performed by putting these materials into a device such as a blender.

[0106] To ensure uniformity, the mixing may be performed using a mixer at 5,000 rpm to 20,000 rpm for 30 seconds to 2 minutes, more specifically at 10,000 rpm to 15,000 rpm for 30 seconds to 1 minute.

[0107] The positive electrode binder is not particularly limited as long as it can be made into fine fibers by the step of preparing the mixed powder. Preferably, it may be a binder containing fluorine to achieve the above-mentioned QBR. The above-mentioned fine fiberization is a process of finely dividing a polymeric polymer, and may be performed, for example, by using mechanical shearing force. As described above, a specific example of such a positive electrode binder is a fluorine-containing polymer, and specifically, it may contain polytetrafluoroethylene (PTFE) alone, or may further contain one or more of PVDF-based copolymers such as PVDF and PVDF-HFP in addition to polytetrafluoroethylene.

[0108] Next, the mixture is kneaded at a temperature in the range of 70° C. to 200° C. under a pressure equal to or higher than normal pressure to produce a mixture mass.

[0109] In conventional technology, high shear mixing such as jet milling was performed to fiberize the positive electrode binder. However, this type of mixing pulverizes the active material, causing problems such as cutting the formed fibers. Therefore, in the present invention, the above problems are solved by using low shear kneading instead of high shear mixing.

[0110] The kneading method is not limited to a specific method. In a specific embodiment of the present invention, the kneading may be performed using, for example, a kneader.

[0111] This kneading is a step in which the positive electrode binder is fibrous and bonds or connects the positive electrode active material and the positive electrode conductive material powder, thereby forming a mixture mass with a solid content of 100%.

[0112] Specifically, the kneading may be controlled at a speed of 10 rpm to 100 rpm. For example, the kneading may be controlled at a speed of 20 rpm or more and 70 rpm or less within the above range. The kneading may be performed for 1 minute to 30 minutes. For example, the kneading may be performed at a speed of 40 rpm to 70 rpm within the above range for 3 minutes to 10 minutes. Meanwhile, the kneading may be controlled at a shear rate in the range of 10 / s to 500 / s. In a specific embodiment of the present invention, the kneading may be performed for 1 minute to 30 minutes, and the shear rate may be controlled in the range of 30 / s to 100 / s.

[0113] Moreover, the kneading step may be carried out under high temperature and pressure conditions equal to or higher than atmospheric pressure, more particularly under pressure conditions higher than atmospheric pressure.

[0114] More specifically, the kneading may be carried out at a temperature in the range of 70°C to 200°C, specifically, 90°C to 150°C.

[0115] If the kneading is performed at a temperature lower than the above temperature range, the positive electrode binder is not easily fibrous and agglomerated by kneading, and it is difficult to form a film during calendaring. Also, if the kneading is performed at an excessively high temperature, the positive electrode binder is rapidly fibrous, and the already formed fibers may be cut by the subsequent excessive shear force, which is undesirable.

[0116] In addition, the kneading may be performed at atmospheric pressure or higher, specifically at 1 to 100 atm, more specifically at 10 to 80 atm. If the pressure range is satisfied, problems such as cutting of fibers formed due to application of excessive shear force and pressure or excessively high density of the mixture mass can be prevented. That is, according to one embodiment of the present invention, the effects intended by the present invention can be obtained when a low shear mixing process is performed under high temperature and pressure conditions higher than atmospheric pressure instead of high shear mixing.

[0117] Next, the mixture mass is pulverized to obtain a mixed powder for the positive electrode. Specifically, the mixture lump produced through the kneading may be immediately calendered, but in that case, the mixture lump must be pressed into a thin film, which may result in an excessively high density of the film or an inconsistent film. Therefore, according to one embodiment of the present invention, the produced mixture lump is subjected to a pulverization step.

[0118] In this case, the grinding step may be performed using equipment such as, but not limited to, a blender or grinder, specifically, at a speed of 5,000 rpm to 20,000 rpm for 30 seconds to 10 minutes, more specifically, at a speed of 10,000 rpm to 18,000 rpm for 30 seconds to 2 minutes.

[0119] If the above-mentioned grinding speed and time are satisfied, the powder can be sufficiently ground to form a powder having a size suitable for film formation, and the problem of a large amount of fine powder being generated from the mixture mass can be prevented. If necessary, a classification process may be performed to remove powder larger or smaller than a certain size.

[0120] Next, the positive electrode mixed powder is placed between a plurality of rolls and calendered to form a positive electrode film.

[0121] 3, in the process 100 of forming a film for a positive electrode, a plurality of rolls 110 are arranged at a distance from each other, and the mixed powder 120 for an electrode obtained in the previous step is put between the adjacent rolls 110, and the rolls 110 rotate in a direction facing each other to roll and form the mixed powder 120 into a sheet or film shape through a powder sheeting step. Then, through multiple calenderings, a film for a positive electrode having a final target thickness is obtained.

[0122] Specifically, such calendering is a step of processing the positive electrode mixed powder into a film shape, for example, a film shape having an average thickness of 50 μm to 300 μm.

[0123] At this time, the calendering may be performed, for example, by rolls positioned facing each other, and at this time, the roll temperature may be 50° C. to 200° C., and the rotation speed ratio of the rolls may be controlled in the range of 1.0 to 2.0.

[0124] By carrying out the calendering step, a dry film for a positive electrode, which acts as a positive electrode mixture, can be manufactured. Conventionally, such a film for a positive electrode is also called a free standing film.

[0125] The film for a positive electrode manufactured in this manner does not contain a solvent, so it has almost no fluidity and is easy to handle, and can be processed into a desired form to be used for manufacturing positive electrodes of various shapes. Furthermore, when the film for a dry positive electrode according to one embodiment of the present invention is used for manufacturing a positive electrode, a drying process for removing the solvent can be omitted, which not only significantly improves the manufacturing processability of the positive electrode but also solves problems such as cracking of the active material and cutting of the fibrous binder that have been problems in manufacturing a conventional dry positive electrode.

[0126] Meanwhile, according to one embodiment of the present invention, there is provided an apparatus for manufacturing a dry electrode, the apparatus including a blender for mixing a raw material composite including an active material, a conductive material, and a fluorine-containing binder, a kneader for kneading the mixture to prepare a mixture mass, a pulverizer for pulverizing the mixture mass to form a mixed powder for an electrode, a calendar for forming the mixed powder for an electrode into a dry electrode film, and a lamination roll for positioning the dry electrode film on at least one side of a current collector and laminating the same.

[0127] The blender is a mixer for mixing raw materials, and can mix the raw materials for the composite at a speed of 5,000 rpm to 20,000 rpm as described above. The kneader is a device for fiberizing the fluorine-containing binder and dispersing the raw materials for the composite, and a mixture can be obtained as a mixture mass by kneading with the kneader. At this time, the kneader for obtaining the results according to the present invention can be set to a range of 70°C to 200°C and a pressure condition of normal pressure or higher. More specifically, it can be set to a pressure condition of 90°C to 180°C and a pressure condition of 1 to 100 atmospheres, more specifically, a pressure condition of 10 to 80 atmospheres.

[0128] The pulverizer is a device for pulverizing the mixture mass to form a mixed powder for an electrode, and may be a blender or a grinder.

[0129] The calender is a device for forming the electrode powder mixture into a film, and may be, for example, a pair of rollers facing each other, and the thickness of the film may be adjusted by adjusting the gap between them.

[0130] The laminating roll serves to attach and roll the dry electrode film formed by the calender onto at least one surface of a current collector. Such a calender and lamination roll can determine the porosity of the dry electrode film according to the present invention.

[0131] That is, the dry electrode manufacturing apparatus according to the present invention is characterized by including a kneader and a pulverizer. The specific structures of the blender, kneader, calender, and lamination roll are well known, and therefore detailed explanations thereof will be omitted in this specification.

[0132] Next, the negative electrode included in the secondary battery according to one embodiment of the present invention will be described. The negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector, the negative electrode active material layer including a plurality of granules that include a negative electrode active material and a negative electrode binder, the negative electrode active material being bound by the negative electrode binder.

[0133] The granules for electrodes of the present invention will be described in detail below. The granules included in the negative electrode include a negative electrode active material and a negative electrode binder. The granules may be composite particles including the negative electrode active material and the negative electrode binder. In addition, as described below, the granules may further include any component that is added as needed together with the negative electrode conductive material. For example, the granules may be composite particles including the negative electrode active material, the negative electrode conductive material, and the negative electrode binder.

[0134] In one embodiment of the present invention, the granule may be a secondary particle obtained by binding two or more negative electrode active material particles with the negative electrode binder and granulating them. In one embodiment of the present invention, the negative electrode active material may mean a particle aggregate, and the diameter of each particle of the negative electrode active material may be 0.05 μm to 2 μm. In one embodiment of the present invention, the negative electrode active material may be 80 wt% or more or 90 wt% or more of the total weight of the granule, and the negative electrode binder may be 20 wt% or less or 10 wt% or less. In one embodiment of the present invention, the granule may further include an electrode conductive material as an optional component, if necessary. The electrode conductive material may be included in the range of 0.1 wt% to 20 wt%, preferably 0.1 wt% to 10 wt%, based on 100 wt% of the granule. For example, the conductive material in the granule may be included in the range of about 0.1 wt% to 5 wt%.

[0135] According to one embodiment of the present invention, the content of the negative electrode active material in the granules may be 85 wt% to 98 wt%. Within the above ranges, the content of the negative electrode binder may be 0.5 wt% to 10 wt%, and the content of the negative electrode conductive material may be 0.5 wt% to 5 wt%. According to another embodiment, the content of the negative electrode active material may be 90 wt% to 98 wt%, the content of the negative electrode binder may be 0.5 wt% to 5 wt%, and the content of the negative electrode conductive material may be 0.5 wt% to 5 wt%.

[0136] FIG. 5 is a schematic diagram of the surface and core of a granule according to one embodiment of the present invention.

[0137] 5, the granule 100 has a larger amount of negative electrode binder contained in a surface portion 102 of the granule than the amount of electrode binder contained in a center portion 101 of the granule. Here, the amount of negative electrode binder may refer to weight or volume.

[0138] In addition to or independently of this, the granule 100 has a negative electrode binder content (wt%) (B c / G t ), the content (wt%) of the negative electrode binder contained in the surface portion 102 of the granules is 100 wt% of the total weight of the granules (B s / G t ) is large. Here, B c is the weight of the binder contained in the core, and B s is the weight of the binder contained in the surface area, and G t means the total weight of the granular particles.

[0139] In addition to or independently of this, the granule 100 has a negative electrode binder content (vol%) (B c / G t ), the content (vol%) of the negative electrode binder contained in the surface portion 102 of the granule relative to the total volume of the granule (100 vol%) (B s / G t ) is large. Here, B c is the volume of the negative electrode binder contained in the center, and B s is the volume of the negative electrode binder contained in the surface area, and G t means the total volume of the granular particles.

[0140] Here, the surface portion means a region near the surface of the granule from the surface of the granule to a predetermined depth toward the center of the granule, and the central portion may mean a portion other than the surface portion. In one embodiment of the present invention, the surface portion may mean a region from 70% of the radius from the center of the granule toward the outside of the granule to the surface of the granule. In one embodiment of the present invention, the surface portion may mean, for example, a region from 80%, 85%, 90%, or 95% of the radius to the surface of the granule.

[0141] In one embodiment of the present invention, the center of the granule may refer to the 1 / 2 point of the longest diameter of the granule.

[0142] In one embodiment of the present invention, the content of electrode binder relative to the total weight (100 wt%) of the granule in the region from the center of the granular particle to the surface of the granule may be 50 wt% or more, 60 wt% or more, 70 wt% or more, 80 wt% or more, or 90 wt% or more.

[0143] In other embodiments of the invention, the content of electrode binder relative to 100 wt% of the total weight of the granule in the region from 95% of the radius from the center of the granular particle to the surface of the granule may be 50 wt% or more, 60 wt% or more, 70 wt% or more, 80 wt% or more, or 90 wt% or more.

[0144] In still other embodiments of the present invention, the content of the negative electrode binder relative to the total weight (100 wt%) of the granule in the region from the center of the granular particle to the surface of the granule may be 50 wt% or more, 60 wt% or more, 70 wt% or more, 80 wt% or more, or 90 wt% or more.

[0145] In one embodiment of the present invention, the content of the negative electrode binder in a region from 90% of the radius from the center of the granular particle to the surface of the granule relative to 100 vol% of the total volume of the granule may be 50 vol% or more, 60 vol% or more, 70 vol% or more, 80 vol% or more, or 90 vol% or more.

[0146] In other embodiments of the present invention, the content of the negative electrode binder in a region from 95% of the radius from the center of the granular particle to the surface of the granule relative to 100 vol% of the total volume of the granule may be 50 vol% or more, 60 vol% or more, 70 vol% or more, 80 vol% or more, or 90 vol% or more.

[0147] In still other embodiments of the present invention, the content of the negative electrode binder relative to 100 vol% of the total volume of the granule in a region from 99% of the radius from the center of the granular particle to the surface of the granule may be 50 vol% or more, 60 vol% or more, 70 vol% or more, 80 vol% or more, or 90 vol% or more.

[0148] To describe the granule in more detail, the granule may have a center portion including a plurality of negative electrode active materials, and a surface portion including a negative electrode binder located on all or a portion of the outside of the center portion and binding the electrode active materials. That is, in the center portion of the granule, a plurality of negative electrode active materials may form an aggregate by making surface contact, line contact, point contact, or two or more contacts with each other, and in the surface portion of the granule, a negative electrode binder may be located on all or a portion of the outside of the aggregate to fix and bind the plurality of negative electrode active materials in the center portion of the granule to each other.

[0149] According to an embodiment of the present invention, a small amount of anode binder may be further included in the center of the granule to connect and fix a plurality of anode active materials in the center. However, as described above, it is preferable that the content of the anode binder is higher in the surface portion than in the center.

[0150] Meanwhile, in one embodiment of the present invention, the granules may have an aspect ratio of 0.5 to 1.0, preferably 0.75 to 1.0. The aspect ratio may mean the ratio of the length of the long axis to the length of the short axis of the granules. In another embodiment of the present invention, the average aspect ratio of the granules may be 0.5 to 1.0, preferably 0.75 to 1.0, in which case the average aspect ratio may mean the ratio of the length of the average long axis to the length of the average short axis of the granular particles. In this case, the average short axis length indicates the average value of the length in the shortest axis direction of the granules, and the average long axis length may indicate the average value of the length in the longest axis direction of the granules. When the aspect ratio of the granules satisfies such a range, it is advantageous in that it has sufficient fluidity suitable for the process.

[0151] Meanwhile, in one embodiment of the present invention, the particle size of the granules may be 0.1 μm to 1,000 μm based on the longest diameter of the particle. In another embodiment of the present invention, the average particle size (D50) of the granules may be 0.1 μm to 1,000 μm.

[0152] According to an embodiment of the present invention, the negative electrode active material layer includes a negative electrode active material and a negative electrode binder having a double bond, and the negative electrode active material layer has a negative electrode quantified binder ratio (QBR) of 2.0 or less, and the negative electrode QBR may be defined by the following Equation 2 (of course, as described above, the negative electrode active material layer may include a negative electrode active material, a negative electrode conductive material, and a negative electrode binder having a double bond). [Formula 2] Negative electrode QBR=ABs / ABf

[0153] In Formula 2, ABs represents the average value of the double bond content of the negative electrode binder in a surface region of the negative electrode active material layer from the outermost surface of the negative electrode active material layer to within 15% of the total thickness of the negative electrode active material layer, and ABf represents the average value of the double bond content of the negative electrode binder in a bottom region of the negative electrode active material layer from the interface of the negative electrode active material layer facing the negative electrode current collector to within 15% of the total thickness of the negative electrode active material layer.

[0154] The negative electrode QBR may be 2.0 or less, 0.6 to 2.0, 0.9 to 2.0, 0.6 to 1.4, 0.6 to 1.4, 0.9 to 1.4, or 0.9 to 1.1. When the negative electrode QBR satisfies such a range, the binder does not migrate to the surface of the negative electrode, so that the content of the negative electrode binder contained in the surface region is not greater than the content of the negative electrode binder contained in the bottom region of the negative electrode active material layer, and the distribution of the binder in the thickness direction of the negative electrode active material layer is uniform, and as a result, the adhesive force between the current collector and the negative electrode active material layer is improved, and the electrical conductivity at the surface of the negative electrode active material layer and the charge / discharge rate therefor are also advantageously increased.

[0155] The negative electrode active material may be carbon such as non-graphitizable carbon or graphitic carbon; Li x Fe2 O 3 (0≦x≦1), Li x WO 2 (0≦x≦1), Sn x Me 1-x Me' y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si), Group 1, 2, 3 elements of the periodic table, halogens; 0≦x≦1; 1≦y≦3; 1≦z≦8) and other metal composite oxides; lithium metal; lithium alloys; silicon-based alloys; tin-based alloys; SiO, SiO / C, SiO 2 Silicon oxides such as SnO, SnO 2 , PbO, PbO 2 , Pb 2 O 3 , Pb 3 O 4 , Sb 2 O 3 , Sb 2 O 4 , Sb 2 O 5 , GeO, GeO 2 , Bi 2 O 3 , Bi 2 O 4 and Bi 2 O 5 metal oxides such as; conductive polymers such as polyacetylene; Li-Co-Ni based materials, etc. may be used.

[0156] The negative electrode binder may include a diene-based polymer, an acrylate-based polymer, a styrene-based polymer, or two or more of them.

[0157] Examples of the diene polymer include polymers containing monomer units derived from conjugated dienes such as butadiene and isoprene, and hydrogenated products thereof. The ratio of monomer units derived from conjugated dienes in the diene polymer may be usually 40% by weight or more, preferably 50% by weight or more, and more preferably 60% by weight or more. Specific examples include conjugated diene homopolymers such as polybutadiene and polyisoprene; aromatic vinyl-conjugated diene copolymers such as styrene-butadiene copolymers (SBR) which may be carboxyl-modified; vinyl cyanide-conjugated diene copolymers such as acrylonitrile-butadiene copolymers (NBR); hydrogenated SBR, hydrogenated NBR, and the like.

[0158] Examples of the acrylate polymer include polymers containing monomer units derived from acrylic acid esters and / or methacrylic acid esters. The ratio of the monomer units derived from acrylic acid esters and / or methacrylic acid esters in the acrylate polymer is usually 40% by weight or more, preferably 50% by weight or more, and more preferably 60% by weight or more. Specific examples of acrylate polymers include crosslinked acrylate polymers such as 2-ethylhexyl acrylate-methacrylic acid-acrylonitrile-ethylene glycol dimethacrylate copolymer, 2-ethylhexyl acrylate-methacrylic acid-methacrylonitrile-diethylene glycol dimethacrylate copolymer, 2-ethylhexyl acrylate-styrene-methacrylic acid-ethylene glycol dimethacrylate copolymer, butyl acrylate-acrylonitrile-diethylene glycol dimethacrylate copolymer, and butyl acrylate-acrylic acid-trimethylolpropane trimethacrylate copolymer; copolymers of ethylene and (meth)acrylic acid ester such as ethylene-methyl acrylate copolymer, ethylene-methyl methacrylate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-ethyl methacrylate copolymer; graft polymers obtained by grafting a radical polymerizable monomer to the copolymer of ethylene and (meth)acrylic acid ester; etc. On the other hand, examples of radical polymerizable monomers used in the graft polymers include methyl methacrylate, acrylonitrile, and methacrylic acid. Additionally, copolymers of ethylene and (meth)acrylic acid, such as ethylene-acrylic acid copolymer and ethylene-methacrylic acid copolymer, can be used as the dispersive binder.

[0159] The styrene-based polymer is a polymer having a repeating unit derived from a styrene monomer, and may be a styrene homopolymer (polystyrene), a styrene copolymer, etc. Examples of the styrene copolymer include block copolymers such as styrene-ethylene-butadiene copolymer, styrene-butadiene-propylene copolymer, styrene-isoprene copolymer, styrene-n-butyl acrylate-itaconic acid-methyl methacrylate-acrylonitrile copolymer, styrene-n-butyl acrylate-itaconic acid-methyl methacrylate-acrylonitrile copolymer, styrene-butadiene block copolymer, styrene-butadiene-styrene block copolymer, styrene-ethylene-butylene-styrene block copolymer, styrene-isoprene block copolymer, and styrene-ethylene-propylene-styrene block copolymer.

[0160] Among these, diene-based polymers and crosslinked acrylate-based polymers are preferred, and crosslinked acrylate-based polymers are particularly preferred, in that they can provide an active material layer that is excellent in adhesion to the current collector and in surface smoothness, and can produce an electrode for an electrochemical element that has high capacitance and low internal resistance.

[0161] The shape of the negative electrode binder is not particularly limited, but it is preferably particulate because it has excellent binding properties and can suppress the decrease in the electrostatic capacity of the produced electrode and deterioration due to repeated charging and discharging. Examples of particulate negative electrode binders include those in which dispersion-type binder particles are dispersed in a solvent such as water, such as latex, and powder-like ones obtained by drying such a dispersion.

[0162] The negative electrode conductive material is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity. For example, graphite such as natural graphite and artificial graphite; carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fiber and metal fiber; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives may be used. More specifically, in order to uniformly mix the conductive material and improve the conductivity, the negative electrode conductive material may include one or more selected from the group consisting of activated carbon, graphite, carbon black, and carbon nanotubes, and more specifically, may include activated carbon.

[0163] According to an embodiment of the present invention, the content of the negative electrode active material may be 85 to 98 parts by weight, and the content of the negative electrode binder may be 0.5 to 10 parts by weight. Also, the content of the negative electrode active material may be 90 to 98 parts by weight, and the content of the negative electrode binder may be 0.5 to 5 parts by weight.

[0164] According to an embodiment of the present invention, the content of the negative electrode active material may be 85 to 98 parts by weight, the content of the negative electrode conductive material may be 0.5 to 5 parts by weight, and the content of the negative electrode binder may be 0.5 to 10 parts by weight. Also, the content of the negative electrode active material may be 90 to 98 parts by weight, the content of the negative electrode conductive material may be 0.5 to 5 parts by weight, and the content of the negative electrode binder may be 0.5 to 5 parts by weight.

[0165] Meanwhile, depending on the case, a filler, which is a component that suppresses expansion of the negative electrode, may be further added to the negative electrode active material layer. The filler is not particularly limited as long as it does not induce chemical changes in the battery and is a fibrous material, and examples of the filler include olefin polymers such as polyethylene and polypropylene; glass fibers, carbon fibers, and other fibrous materials.

[0166] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, calcined carbon, copper, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. In addition, the current collector may have fine irregularities on its surface to increase the adhesive force of the positive electrode active material, and may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0167] A primer layer may be formed on the entirety or a portion of at least one surface of the negative electrode current collector. The primer layer may include a binder and a conductive material, and the sum of the content of the binder and the content of the conductive material in the primer layer may be 90 wt % or more.

[0168] The negative electrode according to an embodiment of the present invention includes a negative electrode active material layer including granules. In this case, the primer layer including a binder and a conductive material has a binder content and a conductive material content of 90% by weight or more, thereby ensuring stability over time of the primer layer and providing excellent physical properties such as adhesive strength and life characteristics, but the present invention is not limited thereto.

[0169] First, the primer layer will be described in detail. According to one embodiment of the present invention, the sum of the content of the binder and the content of the conductive material in the primer layer may be specifically 91 weight % or more, 92 weight % or more, 93 weight % or more, 94 weight % or more, 95 weight % or more, 96 weight % or more, 97 weight % or more, 98 weight % or more, 99 weight % or more, 100 weight % or less, 99 weight % or less, 98 weight % or less, 95 weight % or less, or 93 weight % or less.

[0170] According to an embodiment of the present invention, the primer layer includes a binder and a conductive material, and may further include a dispersant.

[0171] According to another embodiment of the present invention, the primer layer may include a binder and a conductive material, and may be substantially free of a dispersant.

[0172] In this specification, "substantially free" means not only that the component is not contained at all, but also that the component is contained in such a small amount that the function of the component is not realized. For example, the content of the component that is substantially not contained may be 6 wt% or less, 5 wt% or less, 4 wt% or less, 3 wt% or less, 2 wt% or less, 1 wt% or less, 0.5 wt% or less, or 0 wt% (i.e., completely free).

[0173] Thus, the primer layer being "substantially free of dispersant" means not only that the primer layer does not contain any dispersant at all, but also that the primer layer contains a trace amount of dispersant that does not achieve the function of the dispersant, i.e., the function of dispersing the binder and the conductive material. For example, the content of the dispersant in the primer layer may be 6 wt% or less, 5 wt% or less, 4 wt% or less, 3 wt% or less, 2 wt% or less, 1 wt% or less, 0.5 wt% or less, or 0 wt% (i.e., no dispersant at all).

[0174] According to one embodiment of the present invention, the dispersant that is substantially not included may be decomposed when exposed to the atmosphere, which may cause deterioration of the primer layer over time.

[0175] The dispersant may include, but is not limited to, a cellulose-based polymer, an emulsifying surfactant, or two or more of these.

[0176] Examples of the cellulose-based polymer include, but are not limited to, carboxymethyl cellulose (CMC), alkali metal salts of carboxymethyl cellulose, hydroxymethyl cellulose (HMC), alkali metal salts of hydroxymethyl cellulose, hydroxyethyl cellulose (HEC), alkali metal salts of hydroxyethyl cellulose, hydroxypropyl cellulose (HPC), alkali metal salts of hydroxypropyl cellulose, ethyl hydroxyethyl cellulose (EHEC), methyl hydroxymethyl cellulose (MHMC), methyl hydroxyethyl cellulose (MHEC), ethyl hydroxymethyl cellulose (EHMC), methyl cellulose (MC), ethyl cellulose (EC), hydroxypropyl methyl cellulose (HPMC), hydroxyethyl methyl cellulose (HEMC), or a mixture of two or more thereof.

[0177] The emulsifying surfactant may be, for example, a nonionic surfactant, an anionic surfactant, an amphoteric surfactant, or a mixture of two or more thereof, but is not limited thereto. The nonionic surfactant may be, for example, an ethoxylate, an amidoethoxylate, an amine oxide, an alkylglucoside, or a mixture of two or more thereof, but is not limited thereto. The anionic surfactant may be, for example, a phosphate ester, an isothionate, a sulfate, a sulfonate, a taurate, or a mixture of two or more thereof, but is not limited thereto. The amphoteric surfactant may be, for example, a betaine, a glycinate, an alkylamidoalkylamine, or a mixture of two or more thereof, but is not limited thereto.

[0178] According to another embodiment of the present invention, the primer layer may be substantially free of a cellulosic polymer as a dispersant.

[0179] According to yet another embodiment of the present invention, the primer layer may be substantially free of carboxymethylcellulose, hydroxypropylmethylcellulose, or mixtures thereof as a dispersant.

[0180] According to yet another embodiment of the present invention, the primer layer may be substantially free of an emulsifying surfactant.

[0181] According to an embodiment of the present invention, the binder may be a known binder used in a primer layer, but is not particularly limited.

[0182] According to another embodiment of the present invention, it is preferable to use a binder capable of ensuring the stability of the primer layer over time. Specifically, the binder has a glass transition temperature (T g ). More specifically, the glass transition temperature of the binder may be −40° C. to 45° C. The glass transition temperature of the binder may be, for example, −35° C. to 45° C., −30° C. to 40° C., −25° C. to 35° C., −20° C. to 30° C., or −15° C. to 25° C.

[0183] According to yet another embodiment of the present invention, the binder may be, for example, styrene butadiene rubber (SBR), butadiene rubber (BR), nitrile butadiene rubber (NBR), styrene butadiene styrene block polymer (SBS), styrene ethylene butadiene block polymer (SEB), styrene-(styrene butadiene)-styrene block polymer, natural rubber (NR), isoprene rubber (IR), ethylene-propylene-diene terpolymer (EPDM), poly(ethylene-co-propylene-co-5-methylene-2-norbornene), polytetrafluoroethylene (P TFE), polyvinylidene fluoride, polyvinyl chloride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene, polymethyl methacrylate, polyethylhexyl acrylate, polybutyl acrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, polyethylene, polypropylene, ethylene-vinyl acetate copolymer, polyethylene oxide, polypropylene oxide, polyarylate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, or two or more of these. Specifically, the binder may include styrene butadiene rubber (SBR), nitrile butadiene rubber (NBR), polymethyl methacrylate, polyethylhexyl acrylate, polybutyl acrylate, or two or more of these.

[0184] According to yet another embodiment of the present invention, the binder has a glass transition temperature value as mentioned above and may be one or a mixture of two or more selected from the above mentioned types.

[0185] According to yet another embodiment of the present invention, the binder has a glass transition temperature (T g ) and a glass transition temperature (T g ), nitrile butadiene rubber (NBR), or a mixture thereof.

[0186] According to one embodiment of the present invention, the conductive material is 10 2 / g~1,400m 2 For example, the conductive material may have a specific surface area of ​​10 m 2 / g~400m 2 / g or 30m 2 / g~1,400m 2 The specific surface area may be 100 / g.

[0187] According to another embodiment of the present invention, the conductive material has a specific surface area of ​​30 m 2 / g~1,400m 2 / g and may be spherical. In this case, the size of the primary particles of the spherical conductive material may be, for example, 10 nm to 100 nm, specifically 15 nm to 70 nm, but is not limited thereto.

[0188] According to yet another embodiment of the present invention, the conductive material has a specific surface area of ​​10 m 2 / g~400m 2 In this case, the diameter of the cross section of the tubular conductive material in the direction perpendicular to the longitudinal direction may be 0.1 nm to 3 nm, specifically 0.3 nm to 1.5 nm, but is not limited thereto.

[0189] The conductive material is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity. For example, graphite such as natural graphite and artificial graphite; carbon black-based carbon compounds such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives may be used. More specifically, in order to uniformly mix the conductive material and improve the conductivity, the conductive material may include activated carbon, graphite, carbon black, carbon nanotubes, or a mixture of two or more of these, and more specifically, the conductive material may include activated carbon.

[0190] According to one embodiment of the present invention, the primer layer includes the above-mentioned composition and has a thickness of 300 nm to 1.5 μm, specifically, 700 nm to 1.3 μm, but is not limited thereto.

[0191] According to one embodiment of the present invention, The negative electrode is mixing a negative electrode active material and a negative electrode binder with a dispersion medium to prepare a slurry; spray drying the slurry to produce initial granules; Coating the initial granules on a negative electrode current collector; and rolling the applied initial granules to form a negative electrode active material layer including the rolled granules.

[0192] The granules included in the negative electrode active material layer are a result of rolling initial granules prepared by a method including mixing a negative electrode active material and a negative electrode binder with a dispersion medium to prepare a slurry, and spray-drying the slurry. The granules may also be referred to as rolled granules.

[0193] According to an embodiment of the present invention, the slurry may further include a negative electrode conductive material. First, the negative electrode active material, the negative electrode binder, optionally the negative electrode conductive material, and other additives are dispersed or dissolved in a dispersion medium (solvent for the negative electrode binder) to prepare a slurry in which the negative electrode active material, the negative electrode binder, the optional negative electrode conductive material, and other additives are dispersed or dissolved.

[0194] As the dispersion medium used to produce the slurry, water is preferably used, but an organic solvent may be used. Examples of the organic solvent include alkyl alcohols such as methyl alcohol, ethyl alcohol, and propyl alcohol; alkyl ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran, dioxane, and diglyme; amides such as diethylformamide, dimethylacetamide, N-methyl-2-pyrrolidone (NMP), and dimethylimidazolidinone; sulfur-based solvents such as dimethyl sulfoxide and sulfolane; and the like, with alcohols being preferred. By using an organic solvent with a boiling point lower than that of water in combination, the drying speed can be increased during fluidized granulation. In addition, since the dispersibility or solubility of the negative electrode binder can be changed, the viscosity and fluidity of the slurry can be adjusted according to the amount or type of the dispersion medium, thereby improving production efficiency.

[0195] The amount of the dispersion medium used when preparing the slurry may be an amount such that the solids concentration of the slurry is usually in the range of 1 to 50% by weight, or 5 to 50% by weight, or 10 to 30% by weight.

[0196] The method or order of dispersing or dissolving the negative electrode active material and the negative electrode binder in the dispersion medium is not particularly limited, and examples thereof include a method of adding the negative electrode active material and the negative electrode binder to the dispersion medium and mixing them, a method of dissolving or dispersing the negative electrode binder in the dispersion medium and then finally adding the negative electrode active material and mixing them, etc. In this case, as described above, a negative electrode conductive material, other additives, etc. may be selectively added to the dispersion medium.

[0197] Examples of mixing means include mixing equipment such as a ball mill, a sand mill, a bead mill, a pigment disperser, a stone mill, an ultrasonic disperser, a homogenizer, a planetary mixer, etc. Mixing is usually carried out at a temperature range of room temperature to 80° C. for 10 minutes to several hours. The slurry is then spray dried to produce primary granules.

[0198] The spray drying method is a method of spraying and drying a slurry in hot air. The spraying method of the device used in the spray drying method includes a rotating disk method and a nozzle pressurization method. The rotating disk method is a method in which the slurry is introduced into the approximate center of a disk rotating at high speed, and the slurry is positioned on the outside of the disk by the centrifugal force of the disk, at which point it is atomized and dried. The rotation speed of the disk depends on the size of the disk, but is usually 5,000 rpm to 35,000 rpm, preferably 15,000 rpm to 30,000 rpm. On the other hand, the nozzle pressurization method is a method in which the slurry is passed through a thin nozzle and sprayed with a high-pressure fluid such as air or other liquid, and dried by spraying it into a mist.

[0199] In one embodiment of the present invention, the temperature of the hot air may be controlled to 80°C to 250°C based on the inlet temperature of the reactor (at the time of introduction) in order to form a granular structure having a high content of the electrode binder on the surface. In the present invention, the temperature of the hot air may be controlled to preferably 175°C to 220°C, more preferably 180°C to 220°C, taking into consideration the binder content gradient and aspect ratio. In the spray drying method, the method of inhaling the hot air is not particularly limited, and examples thereof include a method in which the hot air and the spray direction flow in parallel in the horizontal direction, a method in which the hot air is sprayed from the top of the drying tower and descends together with the hot air, a method in which the sprayed droplets and the hot air come into countercurrent contact, and a method in which the sprayed droplets first flow in parallel with the hot air and then fall by gravity to come into countercurrent contact. Meanwhile, in one embodiment of the present invention, the outlet temperature of the reactor during the spray drying (the temperature of the hot air discharged from the reactor) may be controlled to 90°C to 130°C.

[0200] If the outlet temperature and / or ΔT, which is the difference between the inlet temperature and the outlet temperature, is low, the drying is not sufficient, and particles with a large amount of residual solvent are formed, so that spherical particles of uniform shape cannot be obtained, and the granules may become solidified or irregular. On the other hand, if the inlet temperature is too high and ΔT is large, granulation may not be possible due to over-drying, and particles with a very small D50 and a low aspect ratio may be generated. Therefore, in order to control the particle size to a suitable level with high sphericity and little binder clumping, it is necessary to control the inlet temperature and outlet temperature within an appropriate range.

[0201] Optionally, the product obtained by spray drying, i.e., the granules, may be heat-treated to harden the surface thereof. The heat treatment temperature may be generally 80°C to 300°C.

[0202] According to one embodiment of the present invention, the initial granules may have a span value of 0.5 to 1.5, or 0.7 to 1.3, as represented by the following formula: Span = (D90-D10) / D50

[0203] Here, D10, D50 and D90 refer to the equivalent circle diameters of the initial granules at 10%, 50% and 90% points of the number cumulative distribution according to the equivalent circle diameter of the initial granules. Here, the equivalent circle diameter (CE diameter) of the initial granules refers to the diameter of a circle having the same area as a two-dimensional image of the initial granule.

[0204] The span value in the above formula is an index showing the distribution (particle size distribution) ratio of the equivalent circle diameter of the initial granules. That is, with respect to the composition ratio of initial granules having different equivalent circle diameters, if the composition ratio of initial granules having an equivalent circle diameter smaller than the average equivalent circle diameter and initial granules having an equivalent circle diameter larger than the average equivalent circle diameter is high, the span value is higher than 1, and if the initial granules are composed only of initial granules having the same equivalent circle diameter as the average equivalent circle diameter, the span value is 0. That is, the smaller the span value in the above formula, the narrower the width of the equivalent circle diameter distribution of the initial granules.

[0205] The initial granules may have an aspect ratio of 0.5 to 1.0, which refers to the ratio of the average major axis length of a granule to the average minor axis length.

[0206] In this case, the average minor axis length refers to the average length of the initial granules in the shortest axial direction, and the average major axis length refers to the average length of the initial granules in the longest axial direction. When the aspect ratio of the initial granules is in this range, it is advantageous in that the granules have sufficient fluidity.

[0207] According to an embodiment of the present invention, the negative electrode may be manufactured by a method including: coating a plurality of granules on a current collector; and rolling the coated plurality of granules to form a negative electrode active material layer.

[0208] The granules prepared by the above-mentioned method are applied onto a current collector, and at least one surface of the current collector may be provided with a primer layer including a conductive material and a binder as described above.

[0209] According to one embodiment of the present invention, a plurality of prepared granules may be fed to a roll-type pressure molding device using a feeder such as a screw feeder to form an active material layer. At this time, the negative electrode current collector may be fed to the rolls of the pressure molding device at the same time as the granules are fed, so that the negative electrode active material layer may be directly laminated on the negative electrode current collector. Alternatively, the granules may be spread on the negative electrode current collector, and the granules may be uniformly cut with a blade or the like to adjust the thickness, and then the negative electrode active material layer may be formed using a pressure device.

[0210] In these methods, the temperature during roll pressure molding is usually 0° C. to 200° C., preferably higher than the melting point or glass transition temperature of the negative electrode binder, and more preferably 20° C. or more higher than the melting point or glass transition temperature. The molding speed in roll pressure molding can usually be 0.1 m / min to 20 m / min, or 1 m / min to 10 m / min. The press line pressure between the rolls can usually be 0.2 kN / cm to 30 kN / cm, or 0.5 kN / cm to 10 kN / cm.

[0211] In order to eliminate the variation in thickness of the molded negative electrode and increase the density of the negative electrode active material layer to increase the capacity, further pressure may be applied as necessary. The post-press method is generally a press process using rolls. In the roll press process, two cylindrical rolls are arranged parallel to each other with a narrow gap between them, and then rotated in opposite directions to sandwich the electrode between them and apply pressure. The temperature of the rolls may be adjusted by heating or cooling, etc.

[0212] According to yet another embodiment of the present invention, there is provided a secondary battery in which an electrode assembly including the positive electrode, the negative electrode, and the separator is housed in a battery case (cylindrical case, prismatic case, pouch, etc.) together with a lithium-containing non-aqueous electrolyte, and an energy storage device including the same as a unit battery.

[0213] The separator may be a conventional porous polymer film used as a separator, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, either alone or in combination. Also, an insulating thin film having high ion permeability and mechanical strength may be used. The separator may include a safety reinforced separator (SRS) in which a ceramic material is thinly coated on the surface of the separator. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high melting point glass fiber, polyethylene terephthalate fiber, etc., may be used, but is not limited thereto.

[0214] The electrolytic solution contains a lithium salt as an electrolyte and an organic solvent for dissolving the lithium salt.

[0215] The lithium salt is not limited as long as it is one that is commonly used in electrolytes for secondary batteries. For example, the anion of the lithium salt may be F - , Cl - , I - , NO 3 - , N(CN) 2- 、BF 4 - 、ClO 4 - 、PF 6 - 、(CF 3 ) 2 PF 4 - 、(CF 3 ) 3 PF 3 - 、(CF 3 ) 4 PF 2 - 、(CF 3 ) 5 PF - 、(CF 3 ) 6 P - 、CF 3 SO 3 - 、CF 3 CF 2 SO 3 - 、(CF 3 SO 2 ) 2 N - 、(FSO 2 ) 2 N - 、CF 3 CF 2 (CF 3 ) 2 CO - 、(CF 3 SO 2 ) 2 CH - 、(SF 5 ) 3 C - 、(CF 3 SO 2 ) 3 C - 、CF 3 (CF 2 ) 7 SO 3 - 、CF 3 CO 2 - 、CH 3 CO 2 - 、SCN -, and (CF 3 CF 2 SO 2 ) 2 N - One selected from the group consisting of:

[0216] The organic solvent contained in the electrolytic solution is not limited as long as it is a commonly used organic solvent, and typically, one or more selected from the group consisting of propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, dipropyl carbonate, dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, vinylene carbonate, sulfolane, γ-butyrolactone, propylene sulfide, and tetrahydrofuran can be used.

[0217] In particular, among the carbonate-based organic solvents, cyclic carbonates such as ethylene carbonate and propylene carbonate are preferred because they are high-viscosity organic solvents with high dielectric constants and can easily dissociate lithium salts in the electrolyte. By mixing such cyclic carbonates with chain carbonates having low viscosity and low dielectric constants such as dimethyl carbonate and diethyl carbonate in an appropriate ratio, an electrolyte solution having high electrical conductivity can be obtained, which can be more preferred.

[0218] Optionally, the electrolyte used in the present invention may further contain additives such as an overcharge inhibitor contained in a conventional electrolyte.

[0219] In the lithium secondary battery according to an embodiment of the present invention, a separator is disposed between a positive electrode and a negative electrode to form an electrode assembly, and the electrode assembly is housed in, for example, a pouch, a cylindrical battery case, or a prismatic battery case, and an electrolyte is then injected to complete the secondary battery. Alternatively, the electrode assemblies may be stacked, impregnated with an electrolyte, and the resulting product may be placed in a battery case and sealed to complete the lithium secondary battery.

[0220] According to one embodiment of the present invention, the secondary battery may include an example of a positive electrode and a negative electrode combination having the following characteristics:

[0221] The secondary battery according to one embodiment of the present invention comprises: a positive electrode including a positive electrode current collector; and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, a positive electrode conductive material, and a positive electrode binder, the positive electrode binder being fibrous to bind the positive electrode active material and the positive electrode conductive material; a negative electrode including: a negative electrode current collector; and a negative electrode active material layer located on the negative electrode current collector, the negative electrode active material layer including a plurality of granules including a negative electrode active material and a negative electrode binder, the negative electrode active material being bound by the negative electrode binder; A separator interposed between the positive electrode and the negative electrode, The positive electrode has a bending resistance of less than 10 mm in diameter (Φ), granules included in the negative electrode have a central portion including a negative electrode active material, and a surface portion located on the whole or part of the outside of the central portion and including a binder binding the negative electrode active material; The binder contained in the surface portions of the plurality of granules may be connected to the binder contained in the surface portions of adjacent granules, so that the binder may be distributed in a network structure within the active material layer.

[0222] The secondary battery according to one embodiment of the present invention comprises: a positive electrode including a positive electrode current collector; and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, a positive electrode conductive material, and a positive electrode binder, the positive electrode binder being fibrous to bind the positive electrode active material and the positive electrode conductive material; a negative electrode including: a negative electrode current collector; and a negative electrode active material layer located on the negative electrode current collector, the negative electrode active material layer including a plurality of granules including a negative electrode active material and a negative electrode binder, the negative electrode active material being bound by the negative electrode binder; A separator interposed between the positive electrode and the negative electrode, The positive electrode binder contained in the positive electrode active material layer has a crystallinity of 10% or less, The granules included in the negative electrode have a central portion including a large number of negative electrode active materials, and a surface portion located on the entire or part of the outside of the central portion and including a binder binding the negative electrode active materials, The binder contained in the surface portions of the plurality of granules may be connected to the binder contained in the surface portions of adjacent granules, so that the binder may be distributed in a network structure within the active material layer.

[0223] The secondary battery according to one embodiment of the present invention comprises: a positive electrode including a positive electrode current collector; and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, a positive electrode conductive material, and a positive electrode binder, the positive electrode binder being fibrous to bind the positive electrode active material and the positive electrode conductive material; a negative electrode including: a negative electrode current collector; and a negative electrode active material layer located on the negative electrode current collector, the negative electrode active material layer including a plurality of granules including a negative electrode active material and a negative electrode binder, the negative electrode active material being bound by the negative electrode binder; A separator interposed between the positive electrode and the negative electrode, the positive electrode active material layer includes a positive electrode active material, a positive electrode conductive material, and a fluorine-based positive electrode binder; the positive electrode active material layer has a positive electrode QBR (Quantified Binder Ratio) of 1.1 or less, The positive electrode QBR is represented by the following formula 1: [Formula 1] Positive electrode QBR=CBs / CBf is defined as In Formula 1, CBs represents an average value of the fluorine content in a surface region of the positive electrode active material layer extending from the outermost surface of the positive electrode active material layer to within 15% of the total thickness of the positive electrode active material layer, CBf represents an average value of the fluorine content in a bottom region of the positive electrode active material layer extending from the interface of the positive electrode active material layer facing the positive electrode current collector to within 15% of the total thickness of the positive electrode active material layer, The granules included in the negative electrode have a central portion including a large number of negative electrode active materials, and a surface portion located on the entire or part of the outside of the central portion and including a binder binding the negative electrode active materials, The binder contained in the surface portions of the plurality of granules may be connected to the binder contained in the surface portions of adjacent granules, so that the binder may be distributed in a network structure within the active material layer.

[0224] The secondary battery according to one embodiment of the present invention comprises: a positive electrode including a positive electrode current collector; and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, a positive electrode conductive material, and a positive electrode binder, the positive electrode binder being fibrous to bind the positive electrode active material and the positive electrode conductive material; a negative electrode including: a negative electrode current collector; and a negative electrode active material layer located on the negative electrode current collector, the negative electrode active material layer including a plurality of granules including a negative electrode active material and a negative electrode binder, the negative electrode active material being bound by the negative electrode binder; A separator interposed between the positive electrode and the negative electrode, The positive electrode has a bending resistance of less than 10 mm in diameter (Φ), In the granules contained in the negative electrode, the content (wt%) of the negative electrode binder relative to the total weight (100 wt%) of the negative electrode active material and the negative electrode binder is higher in the surface portion than in the center portion of the granule, and here, the surface portion may refer to a region near the surface of the granule to a predetermined depth from the surface of the granule toward the center of the granule, and the center portion may refer to a portion other than the surface portion.

[0225] The secondary battery according to one embodiment of the present invention comprises: a positive electrode including a positive electrode current collector; and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, a positive electrode conductive material, and a positive electrode binder, the positive electrode binder being fibrous to bind the positive electrode active material and the positive electrode conductive material; a negative electrode including: a negative electrode current collector; and a negative electrode active material layer located on the negative electrode current collector, the negative electrode active material layer including a plurality of granules including a negative electrode active material and a negative electrode binder, the negative electrode active material being bound by the negative electrode binder; A separator interposed between the positive electrode and the negative electrode, The positive electrode binder contained in the positive electrode active material layer has a crystallinity of 10% or less, In the granules contained in the negative electrode, the content (wt%) of the negative electrode binder relative to the total weight (100 wt%) of the negative electrode active material and the negative electrode binder is higher in the surface portion than in the center portion of the granule, and here, the surface portion may refer to a region near the surface of the granule to a predetermined depth from the surface of the granule toward the center of the granule, and the center portion may refer to a portion other than the surface portion.

[0226] The secondary battery according to one embodiment of the present invention comprises: a positive electrode including a positive electrode current collector; and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, a positive electrode conductive material, and a positive electrode binder, the positive electrode binder being fibrous to bind the positive electrode active material and the positive electrode conductive material; a negative electrode including: a negative electrode current collector; and a negative electrode active material layer located on the negative electrode current collector, the negative electrode active material layer including a plurality of granules including a negative electrode active material and a negative electrode binder, the negative electrode active material being bound by the negative electrode binder; A separator interposed between the positive electrode and the negative electrode, the positive electrode active material layer includes a positive electrode active material, a positive electrode conductive material, and a fluorine-based positive electrode binder; the positive electrode active material layer has a positive electrode QBR of 1.1 or less, The positive electrode QBR is represented by the following formula 1: [Formula 1] Positive electrode QBR=CBs / CBf is defined as In Formula 1, CBs represents an average value of the fluorine content in a surface region of the positive electrode active material layer extending from the outermost surface of the positive electrode active material layer to within 15% of the total thickness of the positive electrode active material layer, CBf represents an average value of the fluorine content in a bottom region of the positive electrode active material layer extending from the interface of the positive electrode active material layer facing the positive electrode current collector to within 15% of the total thickness of the positive electrode active material layer, In the granules contained in the negative electrode, the content (wt%) of the negative electrode binder relative to the total weight (100 wt%) of the negative electrode active material and the negative electrode binder is higher in the surface portion than in the center portion of the granule, and here, the surface portion may refer to a region near the surface of the granule to a predetermined depth from the surface of the granule toward the center of the granule, and the center portion may refer to a portion other than the surface portion.

[0227] The secondary battery according to one embodiment of the present invention comprises: a positive electrode including a positive electrode current collector; and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, a positive electrode conductive material, and a positive electrode binder, the positive electrode binder being fibrous to bind the positive electrode active material and the positive electrode conductive material; a negative electrode including: a negative electrode current collector; and a negative electrode active material layer located on the negative electrode current collector, the negative electrode active material layer including a plurality of granules including a negative electrode active material and a negative electrode binder, the negative electrode active material being bound by the negative electrode binder; A separator interposed between the positive electrode and the negative electrode, The positive electrode has a bending resistance of less than 10 mm in diameter (Φ), A primer layer is formed on all or a part of at least one surface of the negative electrode current collector, the primer layer comprises a binder and a conductive material, The sum of the content of the binder and the content of the conductive material may be 90 wt % or more based on the total weight of the primer layer.

[0228] The secondary battery according to one embodiment of the present invention comprises: a positive electrode including a positive electrode current collector; and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, a positive electrode conductive material, and a positive electrode binder, the positive electrode binder being fibrous to bind the positive electrode active material and the positive electrode conductive material; a negative electrode including: a negative electrode current collector; and a negative electrode active material layer located on the negative electrode current collector, the negative electrode active material layer including a plurality of granules including a negative electrode active material and a negative electrode binder, the negative electrode active material being bound by the negative electrode binder; A separator interposed between the positive electrode and the negative electrode, The positive electrode binder contained in the positive electrode active material layer has a crystallinity of 10% or less, A primer layer is formed on all or a part of at least one surface of the negative electrode current collector, the primer layer comprises a binder and a conductive material, The sum of the content of the binder and the content of the conductive material may be 90 wt % or more based on the total weight of the primer layer.

[0229] The secondary battery according to one embodiment of the present invention comprises: a positive electrode including a positive electrode current collector; and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, a positive electrode conductive material, and a positive electrode binder, the positive electrode binder being fibrous to bind the positive electrode active material and the positive electrode conductive material; a negative electrode including: a negative electrode current collector; and a negative electrode active material layer located on the negative electrode current collector, the negative electrode active material layer including a plurality of granules including a negative electrode active material and a negative electrode binder, the negative electrode active material being bound by the negative electrode binder; A separator interposed between the positive electrode and the negative electrode, the positive electrode active material layer includes a positive electrode active material, a positive electrode conductive material, and a fluorine-based positive electrode binder; the positive electrode active material layer has a positive electrode QBR of 1.1 or less, The positive electrode QBR is represented by the following formula 1: [Formula 1] Positive electrode QBR=CBs / CBf is defined as In Formula 1, CBs represents an average value of the fluorine content in a surface region of the positive electrode active material layer extending from the outermost surface of the positive electrode active material layer to within 15% of the total thickness of the positive electrode active material layer, CBf represents an average value of the fluorine content in a bottom region of the positive electrode active material layer extending from the interface of the positive electrode active material layer facing the positive electrode current collector to within 15% of the total thickness of the positive electrode active material layer, A primer layer is formed on all or a part of at least one surface of the negative electrode current collector, the primer layer comprises a binder and a conductive material, The sum of the content of the binder and the content of the conductive material may be 90 wt % or more based on the total weight of the primer layer.

[0230] The secondary battery according to one embodiment of the present invention comprises: a positive electrode including a positive electrode current collector; and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, a positive electrode conductive material, and a positive electrode binder, the positive electrode binder being fibrous to bind the positive electrode active material and the positive electrode conductive material; a negative electrode including: a negative electrode current collector; and a negative electrode active material layer located on the negative electrode current collector, the negative electrode active material layer including a plurality of granules including a negative electrode active material and a negative electrode binder, the negative electrode active material being bound by the negative electrode binder; A separator interposed between the positive electrode and the negative electrode, The positive electrode has a bending resistance of less than 10 mm in diameter (Φ), the negative electrode binder has a double bond, the negative electrode active material layer has a negative electrode QBR (Quantified Binder Ratio) of 2.0 or less, The negative electrode QBR is represented by the following formula 2: [Formula 2] Negative electrode QBR=ABs / ABf is defined as In Formula 2, ABs represents the average value of the double bond content of the negative electrode binder in a surface region of the negative electrode active material layer from the outermost surface of the negative electrode active material layer to within 15% of the total thickness of the negative electrode active material layer, and ABf represents the average value of the double bond content of the negative electrode binder in a bottom region of the negative electrode active material layer from the interface of the negative electrode active material layer facing the negative electrode current collector to within 15% of the total thickness of the negative electrode active material layer.

[0231] The secondary battery according to one embodiment of the present invention comprises: a positive electrode including a positive electrode current collector; and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, a positive electrode conductive material, and a positive electrode binder, the positive electrode binder being fibrous to bind the positive electrode active material and the positive electrode conductive material; a negative electrode including: a negative electrode current collector; and a negative electrode active material layer located on the negative electrode current collector, the negative electrode active material layer including a plurality of granules including a negative electrode active material and a negative electrode binder, the negative electrode active material being bound by the negative electrode binder; A separator interposed between the positive electrode and the negative electrode, The positive electrode binder contained in the positive electrode active material layer has a crystallinity of 10% or less, the negative electrode binder has a double bond, the negative electrode active material layer has a negative electrode QBR of 2.0 or less, The negative electrode QBR is represented by the following formula 2: [Formula 2] Negative electrode QBR=ABs / ABf is defined as In Formula 2, ABs represents the average value of the double bond content of the negative electrode binder in a surface region of the negative electrode active material layer from the outermost surface of the negative electrode active material layer to within 15% of the total thickness of the negative electrode active material layer, and ABf represents the average value of the double bond content of the negative electrode binder in a bottom region of the negative electrode active material layer from the interface of the negative electrode active material layer facing the negative electrode current collector to within 15% of the total thickness of the negative electrode active material layer.

[0232] The secondary battery according to one embodiment of the present invention comprises: a positive electrode including a positive electrode current collector; and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, a positive electrode conductive material, and a positive electrode binder, the positive electrode binder being fibrous to bind the positive electrode active material and the positive electrode conductive material; a negative electrode including: a negative electrode current collector; and a negative electrode active material layer located on the negative electrode current collector, the negative electrode active material layer including a plurality of granules including a negative electrode active material and a negative electrode binder, the negative electrode active material being bound by the negative electrode binder; A separator interposed between the positive electrode and the negative electrode, the positive electrode active material layer includes a positive electrode active material, a positive electrode conductive material, and a fluorine-based positive electrode binder; the positive electrode active material layer has a positive electrode QBR of 1.1 or less, The positive electrode QBR is represented by the following formula 1: [Formula 1] Positive electrode QBR=CBs / CBf is defined as In Formula 1, CBs represents an average value of the fluorine content in a surface region of the positive electrode active material layer extending from the outermost surface of the positive electrode active material layer to within 15% of the total thickness of the positive electrode active material layer, CBf represents an average value of the fluorine content in a bottom region of the positive electrode active material layer extending from the interface of the positive electrode active material layer facing the positive electrode current collector to within 15% of the total thickness of the positive electrode active material layer, the negative electrode binder has a double bond, the negative electrode active material layer has a negative electrode QBR of 2.0 or less, The negative electrode QBR is represented by the following formula 2: [Formula 2] Negative electrode QBR=ABs / ABf is defined as In Formula 2, ABs represents the average value of the double bond content of the negative electrode binder in a surface region of the negative electrode active material layer from the outermost surface of the negative electrode active material layer to within 15% of the total thickness of the negative electrode active material layer, and ABf represents the average value of the double bond content of the negative electrode binder in a bottom region of the negative electrode active material layer from the interface of the negative electrode active material layer facing the negative electrode current collector to within 15% of the total thickness of the negative electrode active material layer.

[0233] The specific structures of the secondary battery and the energy storage device are well known and will not be described in this specification.

[0234] The present invention will be described in detail below with reference to specific examples. However, the examples according to the present invention can be modified into many other forms, and the scope of the present invention should not be construed as being limited to the following examples. The examples of the present invention are provided to more completely explain the present invention to those skilled in the art.

[0235] <Example 1> (Production of positive electrode) (fiber binder) Lithium nickel cobalt manganese aluminum oxide (NCMA, Li[Ni 0.88 Co 0.07 Mn 0.04 ]Al 0.01 O 296g of ethylenediaminetetraacetate (EDTA), 1g of carbon black as a positive electrode conductive material, and 3g of polytetrafluoroethylene (PTFE) as a positive electrode binder were put into a blender and mixed at 10,000 rpm for 1 minute to prepare a mixture. The temperature of the kneader was stabilized at 150°C, and the mixture was put into the kneader, which was then operated at 50 rpm for 5 minutes under 50 atmospheres to obtain a mixture mass. The mixture mass was put into a blender, pulverized at 10,000 rpm for 30 seconds, and classified using a sieve with a mesh size of 1 mm to obtain a mixed powder for an electrode. The prepared mixed powder for an electrode was then put into a laboratory calender (roll diameter: 88 mm, roll temperature: 100°C) to prepare a film for a positive electrode. Two sheets of the positive electrode film were placed on both sides of an aluminum foil (19 μm) coated with a conductive primer layer in which carbon black and an acrylic binder were mixed in a weight ratio of 5:6, and laminated through a compression roll maintained at 150° C. to prepare a positive electrode.

[0236] At this time, in the lamination step, the compression ratio of the positive electrode film was 35.6%, and the rolling ratio of the positive electrode film was 16.4%.

[0237] Here, the compression ratio of the positive electrode film is defined as the ratio of the thickness to which the positive electrode film is compressed during lamination, and was calculated by the following Equation 1.

[0238] [Formula 1] Compression ratio (%) = T p / T 1 ×100 In formula 1, T p indicates the pressed thickness of the positive electrode film in the lamination stage, T 1 indicates the thickness of the positive electrode film before the lamination step.

[0239] In addition, the rolling ratio of the positive electrode film was defined as a ratio of the thickness of the positive electrode film after the lamination step to the thickness of the positive electrode film before the lamination step, and was calculated by the following Equation 2.

[0240] [Formula 2] Rolling ratio (%) = ((T 1 -T 2 ) / T 1 ×100 In formula 2, T 1 denotes the thickness of the positive electrode film before the lamination step, T 2 indicates the thickness of the positive electrode film after the lamination step.

[0241] The total thickness of the finally produced electrode was 175 μm, the thickness of the electrode active material layer was 77 μm, and the porosity of the electrode was 25.1%.

[0242] In this case, the porosity of the electrode was calculated by subtracting the volume and weight of the current collector from the volume and weight of the electrode to calculate the apparent density of only the electrode active material layer, and the actual porosity of each electrode was calculated according to the following Equation 3 using the true density of each component and the true density calculated based on the composition.

[0243] [Formula 3] Porosity (%) = {1-(apparent density / true density)} x 100

[0244] The increase in apparent density before and after lamination of the positive electrode film and the current collector was 19%.

[0245] In this case, the increase rate of apparent density before and after lamination of the positive electrode film and the current collector was calculated by the following Equation 4. The apparent density before and after lamination of the positive electrode film and the current collector was calculated by measuring the weight and thickness of the positive electrode film before lamination, measuring the weight and thickness of the electrode after lamination, and calculating the weight and thickness of the film by subtracting the weight and thickness of the current collector.

[0246] [Formula 4] Apparent density increase rate (%) = (D 2 -D 1 ) / D 1 ×100 D 1is the apparent density (g / cm) of the positive electrode film before the lamination stage. 3 ), D 2 is the apparent density (g / cm) of the positive electrode film after the lamination step. 3 ) is shown.

[0247] (Production of negative electrodes) (Powder (granules)) (1) Preparation of a current collector with a primer layer Carbon black (specific surface area: 30 m) is used as a conductive material. 2 / g, particle size: 70 nm) 30 parts by weight, styrene butadiene rubber (SBR) (T g A slurry for the primer layer was prepared by mixing 69 parts by weight of ethylenediaminetetraacetate (EPO: -15°C) and 1 part by weight of carboxymethylcellulose (CMC) as a dispersant with water as a dispersion medium. At this time, the content ratio of the conductive material, binder, and dispersant in the slurry was the same as the content ratio of the conductive material, binder, and dispersant in the primer layer formed later. The solid content ratio of the slurry for the primer layer was 7% by weight.

[0248] The prepared primer layer slurry was applied to one side of a copper current collector (thickness: 10 μm) and dried at 130° C. to form a primer layer on one side of the copper current collector. A primer layer was formed on the other side of the current collector using the same solution in the same manner.

[0249] (2) Preparation of granules for negative electrode active material layer A mixture of natural graphite with a sphericity of 0.95 and artificial graphite with an average sphericity of 0.9 as the negative electrode active material, carbon black (Super-C 65) as the negative electrode conductive material, carboxymethylcellulose aqueous solution (Daicel 2200, solid content: 1.5% by weight) as the negative electrode dispersant, and modified styrene butadiene copolymer (Grade Name AX-B119) as the negative electrode binder were mixed with water as the dispersion medium in a weight ratio of 95.6:1.0:1.1:2.3, and a slurry with a viscosity of about 1000 cPs was prepared using a homogenizer. At this time, the solid content in the slurry was 30% by weight. The weight ratio of natural graphite to artificial graphite was 1.91:76.5.

[0250] The prepared slurry was dried using a spray dryer to prepare initial granules having a central portion including a large number of negative electrode active materials and negative electrode conductive materials, and a surface portion located outside the central portion and including a negative electrode binder binding the negative electrode active materials and the negative electrode conductive materials. The conditions of the spray dryer were controlled to a temperature of 180° C. and a rotation speed of 20,000 rpm. Granules 1 were prepared by removing large powders of 150 μm or more from the obtained initial granules using an industrial sieve. Granules 2 were prepared by separating fine powders of less than 40 μm from the granules obtained after spray drying in the preparation method of granules 1 using an industrial sieve.

[0251] Granule 2, which is made of the separated fine powder, was mixed with granule 1, from which only the large powder had been removed, to prepare negative electrode granules (final granules) containing a large amount of fine powder. From the particle size distribution of the final granules thus prepared, D10 was measured to be 32 μm, D50 was measured to be 58 μm, and D90 was measured to be 74 μm.

[0252] (3) Manufacturing of negative electrodes (powder (granules)) Using a device that controls the loading per unit area by adjusting the thickness of the granules, 25 cm 2 The prepared granules were applied to both sides of the current collector having the primer layer so that 400 mg of granules was uniformly applied per layer, and the granules were pressed in a sheeting machine, which is a roll-to-roll hot rolling molding device, at a pressure of 0.7 ton per cm, at 60°C, and at a speed of 2 m per minute to form a negative electrode active material layer, thereby manufacturing a negative electrode.

[0253] At this time, OsO 4 The binder in the obtained granules was stained using OsO 4This was done by reacting with crystals or an aqueous solution, followed by evaporating the reagent. Then, it was mixed with epoxy resin, fixed to a silicone mold, and cured to obtain a granular matrix (see FIG. 6). Next, a cross-sectional sample was made of the granular matrix using an ion milling device (Hitachi IM5000, acceleration voltage: 6 kV). The cross-sectional preparation conditions were an acceleration voltage of 6 kV, an emission current of 400 μA, and the milling time was appropriately adjusted so that the entire mask was not carved. The cross-section of the prepared sample was observed using an SEM photograph and is shown in FIG. 7. Referring to FIG. 7, the granules can be observed to be divided into a surface region with a high binder content from the surface to a certain depth toward the center of the particle, i.e., a central portion (core portion) surrounded by the surface portion.

[0254] (Secondary battery manufacturing) (1) Coin Cell An electrode assembly was manufactured by interposing a porous polyethylene film (thickness: 10 μm) as a separator between the positive and negative electrodes manufactured as described above. The electrode assembly was placed in a coin-type battery case, and LiPF was dissolved in a solvent in which ethylene carbonate, dimethyl carbonate, and diethyl carbonate were mixed in a volume ratio of 1:2:1. 6 A coin cell secondary battery was manufactured by injecting, sealing, and forming using a liquid electrolyte containing 1M of ZnO.

[0255] (2) BuySell Two positive electrodes, one negative electrode, and a porous polyethylene film (thickness: 10 μm) were prepared as the separator, and an electrode assembly was manufactured by stacking the positive electrode / separator / negative electrode / separator / positive electrode in this order. The electrode assembly was then placed in a pouch-type battery case, and LiPF was dissolved in a solvent containing ethylene carbonate, dimethyl carbonate, and diethyl carbonate in a volume ratio of 1:2:1. 6 A bi-cell secondary battery was manufactured by injecting, sealing, and forming the battery using a liquid electrolyte containing 1M of the compound.

[0256] (3) Stack Cell Two negative electrodes, one positive electrode, and a porous polyethylene film (thickness: 10 μm) were prepared as the separator, and an electrode assembly was manufactured by stacking the negative electrode / separator / positive electrode / separator / negative electrode in this order. The electrode assembly was then placed in a pouch-type battery case, and LiPF was dissolved in a solvent containing ethylene carbonate, dimethyl carbonate, and diethyl carbonate in a volume ratio of 1:2:1. 6 A bi-cell secondary battery with the positive electrode located at the center was prepared by injecting, sealing, and forming the battery using a liquid electrolyte containing 1M of ZnO.

[0257] Two positive electrodes, one negative electrode, and a porous polyethylene film (thickness: 10 μm) were prepared as the separator, and an electrode assembly was manufactured by stacking the positive electrode / separator / negative electrode / separator / positive electrode in this order. The electrode assembly was then placed in a pouch-type battery case, and LiPF was dissolved in a solvent containing ethylene carbonate, dimethyl carbonate, and diethyl carbonate in a volume ratio of 1:2:1. 6 A bi-cell secondary battery with the negative electrode located at the center was prepared by injecting, sealing, and forming the battery using a liquid electrolyte containing 1M of ZnO.

[0258] The bicells in which the positive electrode is located at the center (positive electrode type bicells) and the bicells in which the negative electrode is located at the center (negative electrode type bicells) prepared as described above were stacked together with a separator. At this time, four positive electrode type bicells and three negative electrode type bicells were stacked to manufacture stack cells.

[0259] <Comparative Example 1> (Production of positive electrodes) (wet method) As a positive electrode active material, Li[Ni 0.88 Co 0.07 Mn 0.04 ]Al 0.01 O 2), a predispersion of carbon black as a positive electrode conductive material, and polyvinylidene fluoride (PVDF) as a positive electrode binder were added to NMP as a dispersion medium in a weight ratio of 96.5:1.5:2, and the mixture was stirred at 3500 rpm for 1 hour using a homogenizer to prepare a positive electrode active material slurry. The solid content of the carbon black predispersion was 16%, and the final solid content of the slurry was 68%. The slurry was coated on both sides of an aluminum current collector with a thickness of 12 μm, and the coated slurry was dried using a drying device equipped with a hot air blower and an IR heater to form a positive electrode active material layer.

[0260] Thereafter, the positive electrode active material layer was rolled by a roll press method to obtain a dried weight per unit area of ​​590 mg / 25 cm. 2 A positive electrode having a positive electrode active material layer with a loading amount of 1000g / cm2 was prepared.

[0261] (Production of negative electrodes) (wet method) A slurry with a solid content of 45% by weight was prepared by mixing 19.1 parts by weight of natural graphite with an average sphericity of 0.95 and 76.5 parts by weight of artificial graphite with an average sphericity of 0.9 as the negative electrode active material, 1 part by weight of carbon black (Super-C 65) as the negative electrode conductive material, 2.3 parts by weight of styrene butadiene rubber (SBR) as the negative electrode binder, 1.1 parts by weight of carboxymethyl cellulose (CMC) as a binder and thickener, and water as a dispersion medium.

[0262] The slurry was coated on one side of a copper (Cu) thin film, which was a negative electrode current collector having a thickness of 10 μm, and dried in an oven at 120° C. for 20 minutes to form a negative electrode active material layer. The formed negative electrode active material layer was rolled using a roll press method to obtain a dried weight per unit area of ​​400 mg / 25 cm. 2 A negative electrode having a negative electrode active material layer having a loading amount of 1000g / cm2 was prepared.

[0263] (Secondary battery manufacturing) Coin cell, bi-cell and stack cell secondary batteries were manufactured in the same manner as in Example 1, except that the positive electrode and negative electrode manufactured in Comparative Example 1 were used.

[0264] <Comparative Example 2> (Production of positive electrodes) (wet method) A positive electrode was produced in the same manner as in Comparative Example 1. (Production of negative electrodes) (Powder (granules)) A negative electrode was produced in the same manner as in Example 1. (Secondary battery manufacturing) Coin cell, bi-cell and stack cell secondary batteries were manufactured in the same manner as in Example 1, except that the positive electrode and negative electrode manufactured in Comparative Example 2 were used.

[0265] <Comparative Example 3> (Production of positive electrode) (fiber binder) A positive electrode was produced in the same manner as in Example 1.

[0266] (Production of negative electrode) (fiber binder) 96 parts by weight of natural graphite with a sphericity of 0.95 and artificial graphite with an average sphericity of 0.9 (at this time, the weight ratio of natural graphite to artificial graphite is 20:80) as the negative electrode active material, 1 part by weight of carbon black (Super-C 65) as the negative electrode conductive material, and 3 parts by weight of polytetrafluoroethylene (PTFE) as the negative electrode binder were put into a blender and mixed at 10,000 rpm for 1 minute to prepare a mixture. The temperature of the kneader was stabilized at 150°C, and the mixture was put into the kneader, and then operated at a speed of 50 rpm under 50 atmospheres for 5 minutes to obtain a mixture lump. The mixture lump was put into a blender and pulverized at 10,000 rpm for 30 seconds, and classified with a sieve with a mesh size of 1 mm to obtain a mixed powder for an electrode. The prepared mixed powder for an electrode was then put into a laboratory calender (roll diameter: 88 mm, roll temperature: 100°C) to prepare a film for a negative electrode. Two sheets of the negative electrode film were placed on both sides of an aluminum foil (10 μm) coated with a conductive primer layer in which carbon black and an acrylic binder were mixed in a weight ratio of 5:6, and laminated through a compression roll maintained at 150° C. to prepare a negative electrode.

[0267] (Secondary battery manufacturing) Coin cell, bi-cell and stack cell secondary batteries were manufactured in the same manner as in Example 1, except that the positive electrode and negative electrode manufactured in Comparative Example 3 were used.

[0268] <Comparative Example 4> In Comparative Example 4, a positive electrode was produced using granules (powder) for a positive electrode active material layer, and a negative electrode was produced using granules (powder) for a negative electrode active material layer, and an attempt was made to produce a secondary battery using these positive and negative electrodes.

[0269] (Production of positive electrodes) (Powder (granules)) Lithium nickel cobalt manganese aluminum oxide (NCMA, Li[Ni 0.88 Co 0.07 Mn 0.04 ]Al 0.01 O 2 ), carbon black as a positive electrode conductive material, carboxymethylcellulose aqueous solution (Daicel 2200, solid content: 1.5% by weight) as a positive electrode dispersant, and modified styrene butadiene copolymer (Grade Name AX-B119) as a positive electrode binder were mixed with N-methyl-2-pyrrolidone (NMP) as a dispersion medium in a weight ratio of 95.6:1.0:1.1:2.3 to prepare a slurry with a viscosity of about 1000 cPs using a homogenizer. The solid content of the slurry was 68% by weight.

[0270] However, when the produced slurry was subsequently dried using a spray dryer to prepare granules for the positive electrode active material, the high boiling point of the organic solvent NMP posed a risk of explosion, making it impossible to prepare granules for the positive electrode active material. Therefore, it has not been possible to manufacture a positive electrode using the positive electrode active material granules, and a secondary battery including such a positive electrode.

[0271] <Comparative Example 5> (Production of positive electrode) (fiber binder) A positive electrode was produced in the same manner as in Example 1. (Production of negative electrodes) (wet method) A negative electrode was produced in the same manner as in Comparative Example 1. (Secondary battery manufacturing) Coin cell, bi-cell and stack cell secondary batteries were manufactured in the same manner as in Example 1, except that the positive electrode and negative electrode manufactured in Comparative Example 5 were used.

[0272] <Comparative Example 6> (Production of positive electrodes) (wet method) A positive electrode was produced in the same manner as in Comparative Example 1.

[0273] (Production of negative electrode) (fiber binder) 96 parts by weight of natural graphite with a sphericity of 0.95 and artificial graphite with an average sphericity of 0.9 (the weight ratio of natural graphite to artificial graphite is 20:80) as the negative electrode active material, 1 part by weight of carbon black (Super-C 65) as the negative electrode conductive material, and 3 parts by weight of polytetrafluoroethylene (PTFE) as the negative electrode binder were put into a blender and mixed at 10,000 rpm for 1 minute to prepare a mixture. The temperature of the kneader was stabilized at 150°C, and the mixture was put into the kneader, and then operated at a speed of 50 rpm under 50 atmospheres for 5 minutes to obtain a mixture lump. The mixture lump was put into the blender, pulverized at 10,000 rpm for 30 seconds, and classified with a sieve with a mesh size of 1 mm to obtain a mixed powder for the electrode. Thereafter, the prepared electrode mixed powder was put into a lab calendar (roll diameter: 88 mm, roll temperature: 100°C) to prepare a negative electrode film. Two sheets of the negative electrode film were placed on both sides of a copper foil (10 μm) coated with a conductive primer layer in which carbon black and an acrylic binder were mixed in a weight ratio of 5:6, and laminated through a compression roll maintained at 150°C to prepare a negative electrode.

[0274] (Secondary battery manufacturing) Coin cell, bi-cell and stack cell secondary batteries were manufactured in the same manner as in Example 1, except that the positive electrode and negative electrode manufactured in Comparative Example 6 were used.

[0275] <Comparative Example 7> In Comparative Example 7, a positive electrode was produced using granules (powder) for a positive electrode active material layer, and a negative electrode was produced using a wet method, and an attempt was made to produce a secondary battery employing these positive and negative electrodes.

[0276] (Production of positive electrodes) (Powder (granules)) Lithium nickel cobalt manganese aluminum oxide (NCMA, Li[Ni 0.88 Co 0.07 Mn 0.04 ]Al 0.01 O 2 ), carbon black as a positive electrode conductive material, carboxymethylcellulose aqueous solution (Daicel 2200, solid content: 1.5% by weight) as a positive electrode dispersant, and modified styrene butadiene copolymer (Grade Name AX-B119) as a positive electrode binder were mixed with N-methyl-2-pyrrolidone (NMP) as a dispersion medium in a weight ratio of 95.6:1.0:1.1:2.3 to prepare a slurry with a viscosity of about 1000 cPs using a homogenizer. The solid content of the slurry was 68% by weight.

[0277] However, when the produced slurry was subsequently dried using a spray dryer to prepare granules for the positive electrode active material, the high boiling point of the organic solvent NMP posed a risk of explosion, making it impossible to prepare granules for the positive electrode active material. Therefore, it has not been possible to manufacture a positive electrode using the positive electrode active material granules, and a secondary battery including such a positive electrode.

[0278] <Comparative Example 8> In Comparative Example 8, a positive electrode using granules (powder) for a positive electrode active material layer and a negative electrode using a fiberized binder were produced, and an attempt was made to produce a secondary battery employing these positive and negative electrodes.

[0279] (Production of positive electrodes) (Powder (granules)) Lithium nickel cobalt manganese aluminum oxide (NCMA, Li[Ni 0.88 Co 0.07 Mn 0.04 ]Al 0.01 O 2), carbon black as a positive electrode conductive material, carboxymethylcellulose aqueous solution (Daicel 2200, solid content: 1.5% by weight) as a positive electrode dispersant, and modified styrene butadiene copolymer (Grade Name AX-B119) as a positive electrode binder were mixed with N-methyl-2-pyrrolidone (NMP) as a dispersion medium in a weight ratio of 95.6:1.0:1.1:2.3 to prepare a slurry with a viscosity of about 1000 cPs using a homogenizer. The solid content of the slurry was 68% by weight.

[0280] However, when the produced slurry was subsequently dried using a spray dryer to prepare granules for the positive electrode active material, the high boiling point of the organic solvent NMP posed a risk of explosion, making it impossible to prepare granules for the positive electrode active material. Therefore, it has not been possible to manufacture a positive electrode using the positive electrode active material granules, and a secondary battery including such a positive electrode.

[0281] <Performance evaluation> (Secondary battery performance evaluation) The following evaluations were performed on the secondary batteries manufactured in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 5, and Comparative Example 6. In the cases of Comparative Examples 4, 7, and 8, secondary batteries were not manufactured and could not be evaluated. The methods for each evaluation are as follows.

[0282] (1) Initial efficiency evaluation The manufactured coin cell secondary battery was charged at 25°C at a constant current (CC) of 0.1C to 4.2V, then charged at a constant voltage (CV) until the charging current reached 0.005C (cutoff current), and the first charge was performed. After leaving it for 20 minutes, it was discharged at a constant current (CC) of 0.1C to 2.5V. The charge capacity and discharge capacity at this time were measured, and the initial efficiency was calculated using the following formula. Initial efficiency (%) = [(discharge capacity) / (charge capacity)] x 100 The results are shown in Table 1.

[0283] (2) Evaluation of 1C discharge rate The coin cell for which the efficiency evaluation was completed was charged to 4.2V at 0.2C, then cut off at 0.005C (CC (constant current)-CV (constant voltage) charging). After waiting for 20 minutes, it was discharged to 2.5V at a constant current of 1.0C. The discharge capacity at this time was divided by the 0.1C discharge capacity to calculate the rate efficiency. 1C discharge rate = 1.0C discharge capacity / 0.1C discharge capacity

[0284] (3) Evaluation of QC fast charging After completing the rate discharge evaluation, the coin cells were charged and discharged once at 0.2 C to reach an SOC of 0, and then charged at 1.0 C to check the charging curve. The SOC at the third point where the slope of the quadratic differential curve of the charging curve changes from negative to positive was interpreted as the point where lithium ions are deposited in the negative electrode, and was evaluated as the maximum SOC point at which charging at the corresponding C-rate is possible.

[0285] (4) Evaluation of resistance characteristics (SOC50 discharge) The discharge resistance of SOC50 was measured according to the usual monocell evaluation method. That is, the capacity was measured three times at 0.33C, and then the battery was fully charged. The discharge resistance was measured and recorded for each SOC, and the discharge resistance at SOC50 was evaluated.

[0286] (5) Life characteristics (capacity retention rate after 200 cycles) The bi-cell secondary batteries manufactured in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 5 were charged at 25° C. with a constant current and voltage of 0.33 C to 4.2 V with a 0.5% cutoff. Then, the batteries were discharged at a constant current of 0.33 C to 2.5 V. The above charge and discharge behavior was counted as one cycle, and such a cycle was repeated 200 times. At this time, the capacity retention rate was calculated by the following formula. Capacity retention rate = [(Capacity after 200th cycle) / (Capacity after 1st cycle (initial capacity))] × 100 The evaluation results are shown in Table 2.

[0287] (6) Evaluation of initial resistance (SOC50 discharge resistance) The stack cell secondary battery was charged and discharged three times at a rate of 0.33C relative to the design capacity. The SOC was determined based on the third discharge capacity, and charging and discharging were performed at rates of 1.5C and 2.5C. Resistance was evaluated at SOC95, 10, and 5 with a 1.5C pulse, and at SOC80, 50, and 20 with a 2.5C pulse. Between each discharge and charge pulse for resistance measurement, the consumed capacity was replenished with 0.2C. Charge and discharge were performed at a rate of 0.33C between SOC changes, and the pulse measurement unit was measured at short intervals of less than 1 second. The measured voltage drop was divided by the discharge current value to calculate the resistance, and the initial discharge resistance was shown. The evaluation results are shown in Table 3 and FIG.

[0288] (7) Evaluation of initial resistance (SOC50 charging resistor) The initial discharge resistance was measured by the above-mentioned evaluation method, and the charge resistance was calculated by dividing the voltage rise during the charge pulse by the charge current value, to show the initial charge resistance. The evaluation results are shown in Table 3 and FIG.

[0289] (8) Rapid charging evaluation (SOC10 voltage rise) The measurement results of SOC10 in the above initial charging resistance evaluation are shown according to the change in time and voltage. The reason for showing the voltage change in the charging pulse of SOC10 is to predict the resistance change during fast charging when the battery is discharging, and it is possible to know what resistance components affect the fast charging through the time-voltage change. The evaluation results are shown in Table 3 and FIG.

[0290] (9) Evaluation of life characteristics (capacity retention rate after 200 cycles) The stack cell secondary batteries manufactured in Example 1, Comparative Example 1, and Comparative Example 2 were charged at 45° C. with a constant current and voltage of 0.33 C to 4.2 V with a 0.5% cutoff. Then, the batteries were discharged at a constant current of 0.33 C to 2.5 V. The above charge and discharge behavior was counted as one cycle, and such a cycle was repeated 200 times. The capacity retention rate was calculated by the following formula. Capacity retention rate = [(Capacity after 200th cycle) / (Capacity after 1st cycle (initial capacity))] × 100 The evaluation results are shown in Table 3 and FIG.

[0291] [Table 1]

[0292] [Table 2]

[0293] [Table 3]

[0294] 8 to 11, it was confirmed that the secondary battery of Example 1, which is equipped with a positive electrode to which a fiberized binder is applied and a negative electrode to which the granules are used, which are all manufactured by a dry method according to an embodiment of the present invention, has excellent initial efficiency, low initial resistance, and a low voltage rise during charging, which is advantageous for rapid charging, and exhibits improved life characteristics, compared to the secondary batteries of Comparative Example 1, in which the positive electrode and the negative electrode are all manufactured by a wet method, and Comparative Examples 2, 5, and 6, in which one of the positive electrode and the negative electrode is manufactured by a wet method and the other is manufactured by a dry method. Specifically, when a fiberized binder is used in the positive electrode, the electrochemical reaction rate of the positive electrode is increased, but unless the reaction rate of the negative electrode is also increased, it is difficult to fully exhibit the improved electrochemical reaction rate characteristics of the positive electrode. In the secondary battery of Example 1, which has a positive electrode using a fiberized binder and a negative electrode manufactured using the granules, the reaction rate of the negative electrode is also increased, and the electrochemical reaction rate of the positive electrode and the electrochemical reaction rate of the negative electrode are balanced, resulting in a significant improvement in the overall life characteristics of the secondary battery. [Explanation of symbols]

[0295] 10 positive electrode 11 Cathode active material layer 11s surface area 11f bottom area 12 Positive current collector 100 Granules 101 Central part 102 Surface part

Claims

1. a positive electrode including a positive electrode current collector; and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, a positive electrode conductive material, and a positive electrode binder, the positive electrode binder being fibrous to bind the positive electrode active material and the positive electrode conductive material; a negative electrode including: a negative electrode current collector; and a negative electrode active material layer located on the negative electrode current collector, the negative electrode active material layer including a plurality of granules including a negative electrode active material and a negative electrode binder, the negative electrode active material being bound by the negative electrode binder; a separator interposed between the positive electrode and the negative electrode.

2. The secondary battery according to claim 1 , wherein the positive electrode has a bending resistance of less than 10 mm in diameter (Φ).

3. The secondary battery according to claim 2, wherein the flex resistance of the positive electrode is evaluated by a method according to measurement standard JIS K5600-5-1.

4. The flex resistance of the positive electrode is preparing a rectangular positive electrode sample of 100 mm x 50 mm; preparing measuring rods having diameters of 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 8 mm, 10 mm, 12 mm, 16 mm, 20 mm, 25 mm, and 32 mm, bringing the positive electrode sample into contact with the measuring rod having the largest diameter among the measuring rods, and then lifting both ends of the positive electrode sample to determine whether cracks are generated in a composite film of the positive electrode sample; 3. The secondary battery according to claim 2, wherein the secondary battery is evaluated through a step of repeating the step of determining whether or not cracks occur in the composite film of the positive electrode sample in the same manner as in the previous step, if no cracks occur in the previous step, using a measuring rod with a next largest diameter, and determining the minimum diameter value of the measuring rod at which no cracks occur in the composite film of the positive electrode sample as the bending resistance.

5. 2. The secondary battery according to claim 1, wherein the positive electrode active material layer has a porosity of 20% to 35%.

6. The positive electrode active material loading amount of the positive electrode active material layer is 3 mAh / cm 2 ~15mAh / cm 2 The secondary battery according to claim 1 ,

7. The interface resistance between the positive electrode active material layer and the positive electrode current collector is 5 Ω cm 2 The secondary battery according to claim 1 , wherein:

8. The secondary battery according to claim 1 , wherein the positive electrode binder contained in the positive electrode active material layer has a crystallinity of 10% or less.

9. the positive electrode active material layer includes a positive electrode active material, a positive electrode conductive material, and a fluorine-based positive electrode binder; The positive electrode active material layer has a positive electrode QBR (Quantified Binder Ratio) of 1.1 or less, The positive electrode QBR is represented by the following formula 1: [Formula 1] Positive electrode QBR=CBs / CBf is defined as 2. The secondary battery according to claim 1, in which, in Formula 1, CBs represents an average value of the fluorine content in a surface region of the positive electrode active material layer from an outermost surface of the positive electrode active material layer to within 15% of the total thickness of the positive electrode active material layer, and CBf represents an average value of the fluorine content in a bottom region of the positive electrode active material layer from an interface of the positive electrode active material layer facing the positive electrode current collector to within 15% of the total thickness of the positive electrode active material layer.

10. The secondary battery according to claim 1 , wherein the binder contained in the positive electrode active material layer contains polytetrafluoroethylene (PTFE).

11. 2. The secondary battery according to claim 1, wherein the conductive material contained in the positive electrode active material layer comprises activated carbon, graphite, carbon black, Ketjen black, carbon nanotubes, or two or more of these.

12. 2. The secondary battery according to claim 1, wherein the positive electrode active material layer comprises 85 to 98 parts by weight of a positive electrode active material, 0.5 to 5 parts by weight of a conductive material, and 0.5 to 10 parts by weight of a binder.

13. The secondary battery according to claim 1 , wherein the positive electrode current collector is entirely or partially coated with a conductive primer.

14. The secondary battery according to claim 1 , wherein the positive electrode is a dry electrode produced by a dry process.

15. In paragraph 1, The positive electrode is preparing a mixture including a positive electrode active material, a conductive material, and a binder; kneading the mixture at a temperature in the range of 70° C. to 200° C. under a pressure equal to or higher than atmospheric pressure to produce a mixture mass; pulverizing the mixture mass to obtain a positive electrode mixture powder; The positive electrode mixed powder is put between a plurality of rolls and calendered to form a positive electrode film; and laminating the positive electrode film onto a metal current collector.

16. The secondary battery according to claim 15 , wherein the step of kneading to prepare a mixture mass is performed in a kneader under a pressure equal to or higher than atmospheric pressure.

17. The secondary battery according to claim 15, wherein the compression ratio of the positive electrode film in the lamination step is 30% to 50%.

18. The secondary battery according to claim 15 , wherein the rolling ratio of the positive electrode film is 20% or less.

19. The secondary battery according to claim 15, wherein an increase in apparent density between before and after lamination of the positive electrode film and the current collector is 5% to 30%.

20. The secondary battery according to claim 15, wherein the laminating step is performed by a laminating roll at 25°C to 250°C.

21. 2. The secondary battery according to claim 1, wherein the granules contained in the negative electrode have a central portion including the negative electrode active material, and a surface portion located entirely or partially outside the central portion and including a binder that binds the negative electrode active material.

22. The secondary battery according to claim 21 , wherein the binder contained in the surface portions of a number of the granules is connected to the binder contained in the surface portions of adjacent granules, so that the binder is distributed in a network structure within the active material layer.

23. the negative electrode active material layer includes a negative electrode active material and a negative electrode binder, the negative electrode binder has a double bond, the negative electrode active material layer has a negative electrode QBR (Quantified Binder Ratio) of 2.0 or less, The negative electrode QBR is represented by the following formula 2: [Formula 2] Negative electrode QBR=ABs / ABf is defined as 2. The secondary battery of claim 1, wherein, in Formula 2, ABs represents an average value of a double bond content of the negative electrode binder in a surface region of the negative electrode active material layer from an outermost surface of the negative electrode active material layer to within 15% of a total thickness of the negative electrode active material layer, and ABf represents an average value of a double bond content of the negative electrode binder in a bottom region of the negative electrode active material layer from an interface of the negative electrode active material layer facing the negative electrode current collector to within 15% of a total thickness of the negative electrode active material layer.

24. The granules are the content (wt%) of the electrode binder relative to the total weight (100 wt%) of the negative electrode active material and the negative electrode binder is higher in the surface portion than in the center portion; 2. The secondary battery according to claim 1, wherein the surface portion is a region near the surface of the granule from the surface of the granule to a predetermined depth toward the center of the granule, and the central portion is a portion other than the surface portion.

25. 2. The secondary battery according to claim 1, wherein the negative electrode binder comprises a diene-based polymer, an acrylate-based polymer, a styrene-based polymer, or two or more of them.

26. 2. The secondary battery according to claim 1, wherein the negative electrode active material layer comprises a plurality of granules including a negative electrode active material, a negative electrode conductive material, and a negative electrode binder, the negative electrode active material and the negative electrode conductive material being bound by the negative electrode binder.

27. 27. The secondary battery according to claim 26, wherein the negative electrode conductive material comprises activated carbon, graphite, carbon black, Ketjen black, carbon nanotubes, or two or more thereof.

28. 27. The secondary battery according to claim 26, wherein the negative electrode active material layer comprises 85 parts by weight to 98 parts by weight of a negative electrode active material, 0.5 parts by weight to 5 parts by weight of a negative electrode conductive material, and 0.5 parts by weight to 10 parts by weight of a negative electrode binder.

29. A primer layer is formed on all or a part of at least one surface of the negative electrode current collector, the primer layer includes a binder and a conductive material; The secondary battery of claim 1 , wherein a sum of a content of the binder and a content of the conductive material is 90 wt % or more based on a total weight of the primer layer.

30. The negative electrode is mixing a negative electrode active material and a negative electrode binder with a dispersion medium to prepare a slurry; spray drying the slurry to produce initial granules; Spreading the initial granules on a current collector; rolling the applied initial granules to form a negative electrode active material layer including the rolled granules.

31. 31. The secondary battery of claim 30, wherein the slurry further comprises a negative electrode conductive material.

32. An energy storage device comprising the secondary battery according to any one of claims 1 to 31 as a unit battery.

Citation Information

Patent Citations

  • Hole punching apparatus for cylindrical member

    KR102011246B1

  • Electrode for all-solid-state secondary batteries and method for producing same

    WO2013146916A1

  • Electrode sheet for fully solid-state secondary battery, and fully solid-state secondary battery

    WO2019188488A1

  • Electrode for secondary batteries and method for producing same

    WO2021192541A1